Acute Type A Dissection during Pregnancy with Marfan's Syndrome - Heim, Christian; Müller, Philipp; Weyand, Michael; Harig, Frank (Thoracic and Cardiovascular Surgeon Reports, 2021)
Background Marfan's syndrome (MFS) is a connective tissue disorder, caused by a mutation in the FBN-1 gene and affecting multiple organ systems including the vascular system. During pregnancy, women with MFS have an increased risk of aortic dissection due to changes in the cardiovascular system.
CRIS-Team WoS Importer:2021-04-02

A Dual-Pathogen Mitral Valve Endocarditis Caused by Coxiella burnetii and Streptococcus gordonii—Which Came First? - Kaemmerer, Ann-Sophie; Ciotola, Francesco; Geißdörfer, Walter; Harig, Frank; Mattner, Jochen; Seitz, Tatjana; Suleiman, Mathieu; Weyand, Michael; Heim, Christian (Pathogens, 2023)
Infective endocarditis (IE) is still a life-threatening disease with high morbidity and mortality. While usually caused by a single bacterium, poly-microbial infective endocarditis (IE) is rare. Here, we report a (blood-culture-negative) dual pathogen mitral valve IE caused by Coxiella burnetii and Streptococcus gordonii: A 53-year-old woman was presented to an internal medicine department with abdominal pain for further evaluation. Within the diagnostic work up, transthoracic echocardiography (TTE) revealed an irregularly shaped echogenic mass (5 × 13 mm) adherent to the edge of the posterior mitral valve leaflet and protruding into the left atrium. As infected endocarditis was suspected, blood cultures were initially obtained, but they remained negative. Chronic Q fever infection was diagnosed using serologic testing. After the occurrence of cerebral thromboembolic events, the patient was admitted for mitral valve surgery. Intraoperatively, a massively destructed mitral valve with adhering vegetations was noted. Examination of the mitral valve by broad-range bacterial polymerase chain reaction (PCR) and amplicon sequencing confirmed Coxiella burnetii infection and yielded Streptococcus gordonii as the second pathogen. Based on the detailed diagnosis, appropriate antibiotic therapy of both pathogens was initiated, and the patient could be discharged uneventfully on the 11th postoperative day after a successful minimal-invasive mitral valve replacement.
CRIS-Team Scopus Importer:2023-10-20
Keywords: blood-culture-negative endocarditis; Coxiella burnetii; dual-pathogen endocarditis; endocarditis; minimally invasive mitral valve replacement; polymicrobial infective endocarditis; Q fever; Streptococcus gordonii

“Adults with congenital heart defects”: current challenges in medical care. Part II: infective endocarditis, pulmonary hypertension, aortopathy, cardiac surgical aspects, psychocardiology, unresolved problems and future aspects: Position paper of the German Cardiac Society „Erwachsene mit angeborenen Herzfehlern“: Aktuelle Herausforderung in der medizinischen Versorgung Teil II: Infektiöse Endokarditis, pulmonale Hypertonie, Aortopathien, herzchirurgische Aspekte, Psychokardiologie, ungelöste Probleme und Zukunftsaspekte: Positionspapier der Deutschen Gesellschaft für Kardiologie - Kaemmerer, Harald; Baldus, Stephan; Baumgartner, Helmut; Berger, Felix; de Haan, Fokko; Frantz, Stefan; Loßnitzer, Dirk; Uebing, Anselm; Lebherz, Corinna; Weyand, Michael; Diller, Gerhard Paul (Die Kardiologie, 2023)
Despite relevant residual and sequelae, follow-up of adults with congenital heart defects (ACHD) is too often not provided by/at specialized and/or certified physicians or medical centers, even though significant problems may develop in the long-term course. In addition to specific CHD related residua, heart failure and arrhythmias, major problem constellations include infective endocarditis, pulmonary vascular disease, and pulmonary hypertension and aortopathy. In addition, there are cardiac and noncardiac comorbidities, including psychological burdens. This position paper of the German Cardiac Society provides up to date information on these problems and emphasizes the urgent need for experienced follow-up by specialized physicians or hospitals, as treatment regimens of acquired heart disease cannot entirely be transferred to CHD. In addition, the need for primary and secondary medical prevention is emphasized to reduce the burden of disease as well as the socioeconomic burden and costs in this particular patient population.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Adult; Aortopathies; Cardiac surgery; Congenital heart disease; Follow-up; Infective endocarditis; Psychocardiology; Pulmonary hypertension

Amphetamine Abuse as a Rare Cause of Recurrent LVAD Pump Thrombosis - Heim, Christian; Kondruweit, Markus; Weyand, Michael; Tandler, Rene (Journal of Cardiac Surgery, 2015)
We report a patient with recurrent left ventricular assist device (LVAD) thrombosis due to amphetamine addiction. The management of this complication is reviewed. doi: 10.1111/jocs.12504 (J Card Surg 2015;30:215-216).
EVALuna2:16091

A new ex vivo beating heart model to investigate the application of heart valve performance tools with a high-speed camera - Kondruweit, Markus; Friedl, Sven; Heim, Christian; Wittenberg, Thomas; Weyand, Michael; Harig, Frank (Asaio Journal, 2014)
High-speed camera examination of heart valves is an established technique to examine heart valve prosthesis. The aim of this study was to examine the possibility to transmit new tools for high-speed camera examination of heart valve behavior under near-physiological conditions in a porcine ex vivo beating heart model. After explantation of the piglet heart, main coronary arteries were cannulated and the heart was reperfused with the previously collected donor blood. When the heart started beating in sinus rhythm again, the motion of the aortic and mitral valve was recorded using a digital high-speed camera system (recording rate 2,000 frames/sec). The image sequences of the mitral valve were analyzed, and digital kymograms were calculated at different angles for the exact analysis of the different closure phases. The image sequence of the aortic valve was analyzed, and several snakes were performed to analyze the effective orifice area over the time. Both processing tools were successfully applied to examine heart valves in this ex vivo beating heart model. We were able to investigate the exact open and closure time of the mitral valve, as well as the projected effective orifice area of the aortic valve over the time. The high-speed camera investigation in an ex vivo beating heart model of heart valve behavior is feasible and also reasonable because of using processing feature such as kymography for exact analysis. These analytical techniques might help to optimize reconstructive surgery of the mitral valve and the development of heart valve prostheses in future.
EVALuna2:16086

ANTAGONISM OF PLATELET-DERIVED SEROTONIN (5-HT) MODULATES MACROPHAGE-MEDIATED TRANSPLANT VASCULOPATHY AFTER AORTIC TRANSPLANTATION BUT NOT LARGE AIRWAY REMODELING IN MURINE TRACHEAL ALLOGRAFTS - Bujnoch, Daniel; Gocht, A.; Distler, Jörg; Spriewald, B.; Ramsperger-Gleixner, Martina; Weyand, Michael; Ensminger, S.; Heim, Christian (2018)
EVALuna2:34953

Aortic annulus eccentricity before and after transcatheter aortic valve implantation: Comparison of balloon-expandable and self-expanding prostheses - Schuhbaeck, Annika; Weingartner, Christina; Schmid, Jasmin; Pflederer, Tobias; Rixe, Johannes; Nef, Holger; Schneider, Christian; Lell, Michael; Uder, Michael; Ensminger, Stephan; Feyrer, Richard; Weyand, Michael; et al. (European Journal of Radiology, 2015)
The geometry of the aortic annulus and implanted transcatheter aortic valve prosthesis might influence valve function. We investigated the influence of valve type and aortic valve calcification on post-implant geometry of catheter-based aortic valve prostheses.Eighty consecutive patients with severe aortic valve stenosis (mean age 82 ± 6 years) underwent computed tomography before and after TAVI. Aortic annulus diameters were determined. Influence of prosthesis type and degree of aortic valve calcification on post-implant eccentricity were analysed.Aortic annulus eccentricity was reduced in patients after TAVI (0.21 ± 0.06 vs. 0.08 ± 0.06, p<0.0001). Post-TAVI eccentricity was significantly lower in 65 patients following implantation of a balloon-expandable prosthesis as compared to 15 patients who received a self-expanding prosthesis (0.06 ± 0.05 vs. 0.15 ± 0.07, p<0.0001), even though the extent of aortic valve calcification was not different. After TAVI, patients with a higher calcium amount retained a significantly higher eccentricity compared to patients with lower amounts of calcium.Patients undergoing TAVI with a balloon-expandable prosthesis show a more circular shape of the implanted prosthesis as compared to patients with a self-expanding prosthesis. Eccentricity of the deployed prosthesis is affected by the extent of aortic valve calcification.
EVALuna2:12030

A Practical Approach to Systemic Mastocytosis Complications in Cardiac Surgery: A Case Report and Systematic Review of the Literature - Suleiman, Mathieu; Brückl, Valeska; Fechner, Jörg; Kaemmerer, Ann-Sophie; Wilk, Florian; Weyand, Michael; Harig, Frank (Journal of Clinical Medicine, 2023)
(1) Background: Systemic mastocytosis is a rare, non-curable disease with potential life-threatening complications in patients receiving cardiac surgery. (2) Methods: This systematic review of the literature was prompted by the case of a life-threatening anaphylactic reaction during cardiac surgery related to systemic mastocytosis. The search of all types of studies, using several databases (Pubmed, Scopus and Web of Science), was conducted through September 2022 to identify the relevant studies. (3) Results: Twelve studies were included describing cases of patients undergoing cardiac surgery who were diagnosed with systemic mastocytosis. An adverse effect, namely anaphylaxis, has happened in three cases. Different strategies of premedication, intraoperative and postoperative management were used. In our case, the patient was admitted for elective biological aortic valve replacement due to severe aortic stenosis. Intraoperatively, the patient developed an anaphylactic shock during the administration of protamine after separation from the cardiopulmonary bypass. This anaphylaxis reaction was a complication of the pre-existing systemic mastocytosis and could be successfully managed by the administration of epinephrine, antihistamines and corticosteroids. (4) Conclusions: This systematic literature search and case report highlight the importance of careful preoperative planning, as well as coordination between cardiac surgeons, anesthesiologists and hemato-oncological specialists, in patients with rare but complication-prone diseases such as systemic mastocytosis.
CRIS-Team WoS Importer:2023-03-10

Assessing psychosocial vulnerability and care needs of pretransplant patients by means of the INTERMED - Ludwig, Gundula; Dobe-Tauchert, Perdita; Nonnast-Daniel, Barbara; Stiefel, Friedrich; De Jonge, Peter; Lobo, Elena; Richter, Rainer; Eckardt, Kai-Uwe; Hohenberger, Werner; Weyand, Michael; Soellner, Wolfgang (Zeitschrift für Psychosomatische Medizin und Psychotherapie, 2014)
We investigated whether the INTERMED, a generic instrument for assessing biopsychosocial case complexity and direct care, identifies organ transplant patients at risk of unfavourable post-transplant development by comparing it to the Transplant Evaluation Rating Scale (TERS), the established measure for pretransplant psychosocial evaluation.One hundred nineteen kidney, liver, and heart transplant candidates were evaluated using the INTERMED, TERS, SF-36, EuroQol, Montgomery-Åsberg Depression Rating Scale (MADRS), and Hospital Anxiety & Depression Scale (HADS).We found significant relationships between the INTERMED and the TERS scores. The INTERMED highly correlated with the HADS,MADRS, and mental and physical health scores of the SF-36 Health Survey.The results demonstrate the validity and usefulness of the INTERMED instrument for pretransplant evaluation. Furthermore, our findings demonstrate the different qualities of INTERMED and TERS in clinical practice. The advantages of the psychiatric focus of the TERS and the biopsychosocial perspective of the INTERMED are discussed in the context of current literature on integrated care.
EVALuna2:3696

Better Late Than Never - A Case of a Congenital Left Partial Anomalous Pulmonary Venous Drainage Diagnosed and Treated in The Sixth Decade of Life - Elbayomi, Mohamed; Pathare, Presheet; Nooh, Ehab; Harig, Frank; Abdullayev, Farid; Weyand, Michael (Heart Surgery Forum, 2023)
Partial anomalous pulmonary venous drainage (PAPVD) is a relatively uncommon cardiac anomaly. The diagnosis might be challenging as are the presenting symptoms. Its clinical course mimics more familiar diseases, e.g., pulmonary artery embolism. We present a case of PAPVD, which had been misdiagnosed for more than two decades. After establishing the correct diagnosis, the patient got his congenital anomaly surgically corrected and showed excellent cardiac recovery in the six months follow up.
CRIS-Team Scopus Importer:2023-04-07

Bioelectrical Impedance Analysis as a Contemporary Biomarker of Obesity in Adults with Marfan- or Loeys-Dietz-Syndrome - Freilinger, Sebastian; Suleiman, Mathieu; Bischoff, Gert; Ewert, Peter; Freiberger, Annika; Huntgeburth, Michael; Kaemmerer, Ann-Sophie; Schopen, Judith; Meierhofer, Christian; Nagdyman, Nicole; Kaemmerer, Harald; Weyand, Michael; et al. (Reviews in Cardiovascular Medicine, 2022)
Background: It is clinically widely overlooked that many patients with Marfan- (MFS) or Loeys-Dietz-Syndrome (LDS) are obese. While anthropometric routine parameters are not very suitable, the modern Bioelectrical Impedance Analysis (BIA) seems superior for the acquisition of reliable noninvasive assessment of body composition of patients. The aim of the study was to assess the body composition of patients with MFS/LDS by BIA in order to detect occult obesity, which may be a risk marker for aortic or vascular complications. Methods: In this exploratory cross-sectional study, 50 patients (66% female; mean age: 37.7 +/- 11.7 [range: 17-64] years) with a molecular genetic (n= 45; 90%) or clinical (n= 5; 10%) proven diagnosis of MFS or LDS were enrolled between June 2020 and February 2022. All BIA-measurements were performed with the Multifrequence-Impedance-Analyzer Nutriguard-MS (Data Input, Poecking, Germany). Results: The MFS/LDS collective was significantly different from an age-, sex-, and BMI-adjusted control in terms of body fat, percent cell ularity, body cell mass, extra cellular mass/body cell mass index, and phase angle (all p < 0.05). The mean I31A-measured bodyfat was 31.7 +/- 8.7% [range: 9.5.-53.5%], while the mean calculated 13MI of the included patients was 23.0 +/- 4.8 kg/m(2) [range: 15.2-41.9 kg/m(2)]. Therefore, using the obesity cut-off values for the body fat percentage of 25% in men and 35% in women, the BIA classifies as many as 28 patients (56.0%) as obese. In contrast only 12 patients (24.0%) were pre-obese, respectively 3 (6.0%) obese by BMI. The significant difference (p < 0.001) had an accordance of 42.7%. Overall, 15 patients (13 MFS; 2 LDS) had previous aortic surgery (n=14) and/or interventional treatment (n=2) for aortic complications (aneurysm, aortic dissection). 11 out of these 15 (73.3%) were currently classified as obese by BIA. Conclusions: The fact that many patients with MFS or LDS are obese is widely unknown, although obesity may be associated with impaired vascular endothelial function and an increased risk of cardiovascular complications. Also, in patients with MFS/I.DS, INA allows a reliable assessment of the body composition beyond the normal anthropometric parameters, such as BMI. In the future, BIA-data possibly may be of particular i mportance for the assessment of the vascular risk of MFS/LDS patients, besides the aortic diameters.
CRIS-Team WoS Importer:2022-07-22

Blockade of Tyrosine Kinases as Preventive Strategy Against Cardiac Allograft Vasculopathy in a Murine Aortic Transplant Model - Gocht, Annika; Distler, Jörg; Spriewald, Bernd; Ramsperger-Gleixner, Martina; Ensminger, Stephan M.; Weyand, Michael; Heim, Christian (2018)
EVALuna2:34976

Calcified Amorphous Tumor and Granulomatosis with Polyangiitis—Case Report and Systematic Review of the Literature - Suleiman, Mathieu; Agaimy, Abbas; Dewald, Oliver; Kaemmerer-Suleiman, Ann-Sophie; Mellert, Fritz; Weyand, Michael; Harig, Frank (Journal of Clinical Medicine, 2025)
Background: Calcified amorphous tumor (CAT) is a rare, mostly incidental tumor-like cardiac lesion of unknown histogenesis. Current imaging modalities do not differentiate between CAT and other masses. As it can be a source for embolization, surgical excision of CAT is mandatory. CAT in patients with Granulomatosis with polyangiitis (GPA) is exceedingly rare. Methods: This systematic literature review was prompted by the case of a CAT in a patient with GPA. The search of all types of studies in two databases (PubMed and Scopus) was conducted through November 2024 to identify the relevant studies. Results: Nine studies were included describing cases of patients being diagnosed with GPA and a cardiac mass. All included patients had a histopathological examination of the either biopsied or surgically resected mass. Only one case reported a CAT. In our case, the patient was diagnosed with GPA through a kidney biopsy, whereas a cardiac mass in the right atrium was diagnosed by echocardiography during evaluation for possible kidney transplantation. One year later a progression was observed, and the mass was resected. The histopathological examination revealed a CAT. The patient could be successfully discharged in a good clinical condition. Conclusions: This systematic literature search and case report highlight the importance of regular echocardiographic examination in patients with GPA. Moreover, surgical excision is crucial for the diagnosis and for further therapy planning, regardless of whether the mass is neoplastic or not.
CRIS-Team Scopus Importer:2025-01-31
Keywords: calcified amorphous tumors; cardiac mass; CAT; granulomatosis with polyangiitis (GPA); Wegener’s granulomatosis

Cardiac allograft vasculopathy after heart transplantation: Current state of knowledge on diagnosis and treatment Transplantatvaskulopathie nach Herztransplantation: Aktueller Wissensstand zu Diagnose und Therapie - Kuckhahn, Annika; Ramsperger-Gleixner, Martina; Ensminger, Stephan; Weyand, Michael; Heim, Christian (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2019)
Chronic rejection with its characteristic feature of cardiac allograft vasculopathy (CAV) is one of the major complications after successful heart transplantation and cannot be prevented by the currently used standard immunosuppressants. This review article describes the epidemiology of CAV and the pathogenesis of this multifactorial process that leads to the development of a neointima consisting mainly of vascular smooth muscle cells. Additionally, current diagnostic procedures for cardiac allograft vasculopathy are depicted. The diffuse distribution of vascular alterations combined with the mostly delayed development of clinical symptoms hampers the diagnosis of CAV. In the last few years various approaches for treatment and prevention of CAV were described and evaluated using preclinical models. An important animal model to investigate new options is abdominal aortic transplantation in mice. Such models demonstrated that cytomegalovirus infection is of great importance for CAV development. In addition, the administration of the platelet aggregation inhibitor clopidogrel, especially in combination with a mechanistic target of rapamycin (mTOR) inhibitor, could attenuate CAV formation. Moreover, ischemic preconditioning showed positive results. In some studies, the treatment with direct anti-proliferative substances achieved promising results to delay the development of CAV. The experimental approaches in animals need to be evaluated for safety and efficacy in clinical studies in order to improve postoperative long-term survival of heart transplantation patients in the future.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cytomegalovirus; Ischemic preconditioning; Neointima; Platelet aggregation inhibitors; Transplant rejection

Changes in sternal perfusion following internal mammary artery bypass surgery - Taeger, Christian; Klein, Konstantin; Horch, Raymund E.; Weyand, Michael; Beier, Justus (Clinical Hemorheology and Microcirculation, 2017)
BACKGROUND: Coronary bypass surgery using the internal mammary artery (IMA) is among the most commonly performed procedures in treatment of advanced coronary vessel disease. Further, bilateral harvesting of the IMA is associated with increased rates of sternal wound infections. OBJECTIVE: This study aimed to explore changes in sternal perfusion, following left internal mammary artery (LIMA) harvesting. METHODS: 60 patients were divided equally into intervention- and control cohorts and underwent assessment of oxygen saturation (sO2) and relative blood flow (RBF) by laser doppler flowmetry remission spectroscopy preoperatively, 24 h and 72 h postoperatively. RESULTS: 24 h postoperatively a significant decrease of sO2 and RBF could be detected in LIMA harvest patients. After 72 h this difference disappeared. The side comparison within the groups 24 h postoperatively revealed a reduction of sO2 on the LIMA side within both groups. Regarding the 24 h RBF in side comparison, no significant differences could be detected within the groups. The 72 h side comparison showed an increased RBF for the non-LIMA side within the control group. CONCLUSIONS: The use of the LIMA may lead to significant decreases in local tissue oxygen saturation and RBF. This reduction is mostly distinct within the first 3 days postoperatively and may influence sternal wound infections.
EVALuna2:32852

Chronic rejection after lung transplantation Overview and experimental approaches for long-term organ protection - Gräbner, Cindy; Ramsperger-Gleixner, Martina; Kuckhahn, Annika; Weyand, Michael; Heim, Christian (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2023)
Background Following lung transplantation (LTx) 50% of all patients develop chronic rejection within 5 years of transplantation in the form of a chronic lung allograft dysfunction (CLAD). To date, the processes of chronic transplant failure are not curable with medication.Material and method After illustrating the different phenotypes and pathogenesis of CLAD, this review focuses on the diagnostic and treatment options. New clinical and experimental treatment approaches for CLAD are discussed.Results For research of new experimental treatment options, animal models are being used. The established model for CLAD research is the orthotopic tracheal transplantation in mice. Using this model, the influence of the chemokine receptor M33 of the murine cytomegalovirus on the development of chronic rejection and its persistence in the body could be shown. Furthermore, the antiplatelet agent clopidogrel, the mTOR inhibitor everolimus and the tyrosine kinase inhibitor nintedanib reduced the development of the rejection-induced histological changes in tracheal allografts in mouse models.Conclusion The successful experimental approaches show potential treatment approaches, which counteract the development of a CLAD and have to go through clinical trials before they can be used on patients after lung transplantation.
CRIS-Team WoS Importer:2023-03-10

Clopidogrel significantly lowers the development of atherosclerosis in ApoE-deficient mice in vivo - Heim, Christian; Gebhardt, Julia; Ramsperger-Gleixner, Martina; Jacobi, Johannes; Weyand, Michael; Ensminger, Stephan M. (Heart and Vessels, 2016)
The anti-platelet drug clopidogrel has been shown to modulate adhesion molecule and cytokine expression, both playing an important role in the pathogenesis of atherosclerosis. The aim of this study was to investigate the impact of clopidogrel on the development and progression of atherosclerosis. ApoE(-/-) mice fed an atherogenic diet (cholesterol: 1 %) for 6 months received a daily dose of clopidogrel (1 mg/kg) by i.p. injection. Anti-platelet treatment was started immediately in one experimental group, and in another group clopidogrel was started 2 month after beginning of the atherogenic diet. Blood was analysed at days 30, 60 and 120 to monitor the lipid profile. After 6 months the aortic arch and brachiocephalic artery were analysed by Sudan IV staining for plaque size and by morphometry for luminal occlusion. Serum levels of various adhesion molecules were investigated by ELISA and the cellular infiltrate was analysed by immunofluorescence. After daily treatment with 1 mg/kg clopidogrel mice showed a significant reduction of atherosclerotic lesions in the thoracic aorta and within cross sections of the aortic arch [plaque formation 55.2 % (clopidogrel/start) vs. 76.5 % (untreated control) n = 8, P < 0.05]. After treatment with clopidogrel P-/E-selectin levels and cytokine levels of MCP-1 and PDGF? were significantly reduced as compared to controls. The cellular infiltrate showed significantly reduced macrophage and T-cell infiltration in clopidogrel-treated animals. These results show that clopidogrel can effectively delay the development and progression of 'de-novo' atherosclerosis. However, once atherosclerotic lesions were already present, anti-platelet treatment alone did not result in reverse remodelling of these lesions.
EVALuna2:16107

Clopidogrel significantly lowers the development of atherosclerosis in ApoE-deficient mice in vivo - Heim, Christian; Gebhardt, Julia; Ramsperger-Gleixner, Martina; Jacobi, Johannes; Weyand, Michael; Ensminger, Stephan M. (Heart and Vessels, 2016)

Combination of clopidogrel and everolimus completely abolished the development of transplant arteriosclerosis - Eckl, S.; Heim, Christian; Abele-Ohl, S.; Hoffmann, J.; Weyand, M.; Ensminger, S. M.; Weyand, Michael (Transplantationsmedizin, 2009)
Introduction: Our group has previously shown that platelet inhibition with clopidogrel reduced the formation of transplant arteriosclerosis (TxA). The aim of this study was to investigate whether a combination of cyclosporine or everolimus with clopidogrel has a beneficial effect on the development of TxA. Methods: Fully allogeneic C57BL/6 (H2b) donor aortas were transplanted into CBA (H2k) recipients. Recipient mice were treated with cyclosporine (2mg/kg/d) and everolimus (0,05mg/kg/d) alone or in combination with clopidogrel (1mg/kg/d). Grafts were analysed by histology and morphometry on day 30 after transplantation. Results: In mice treated with clopidogrel alone, TxA was reduced as compared to untreated controls (intima proliferation 57%+/-13% vs. 79%+/-8% [control]/n=5). Daily application of everolimus significantly reduced the development of TxA compared to untreated controls (intima proliferation of 27% +/- 10% vs. 79% +/-8% [control], n=5). Strikingly, combination of clopidogrel and everolimus almost completely abolished the formation of TxA (intima proliferation: 14% +/- 10% vs. 79% +/- 8% [control], n = 5). In contrast, daily application of cyclosporine alone did not reduce the development of TxA compared to controls (intima proliferation: 74% +/- 7% vs. 79% +/- 8% [control], n=5). In addition combination of cyclosporine and clopidogrel compared with clopidogrel alone showed no additive effect. Conclusion: These results demonstrate that combination of clopidogrel and everolimus can completely abolish the development of TxA in a mouse aortic allograft model. Our findings have also important clinical implications as patients suffering from TxA after cardiac transplantation may benefit from treatment with a combination of these drugs.
CRIS-Team Scopus Importer:2024-06-04

Combination of clopidogrel and everolimus dramatically reduced the development of transplant arteriosclerosis in murine aortic allografts - Eckl, Sebastian; Heim, Christian; Abele-Ohl, Silke; Hoffmann, Julia; Ramsperger-Gleixner, Martina; Weyand, Michael; Ensminger, Stephan M. (Transplant International, 2010)
Summary Our group has shown that platelet inhibition with clopidogrel, an antagonist of the P2Y12 adenosine diphosphate receptor on platelets, reduced the formation of transplant arteriosclerosis. The aim of this study was to investigate whether a combination of cyclosporin or everolimus with clopidogrel has a beneficial effect on the development of transplant arteriosclerosis. Fully MHC mismatched C57Bl/6 (H2b) donor aortas were transplanted into CBA.J (H2k) recipients and mice received either clopidogrel alone (1 mg/kg/day) or in combination with cyclosporin (2 mg/kg/day) or everolimus (0.05 mg/kg/day). Grafts were analysed by histology and morphometry on day 30 after transplantation. In mice treated with clopidogrel alone, transplant arteriosclerosis was significantly reduced [intima proliferation 56 ± 11% vs. 81 ± 7% (control)/n = 7]. Daily application of everolimus reduced the development of transplant arteriosclerosis compared with untreated controls [intima proliferation of 29 ± 9% vs. 81 ± 7% (control)/n = 7]. Strikingly, combination of clopidogrel and everolimus almost abolished the formation of transplant arteriosclerosis [intima proliferation: 11 ± 8% vs. 81 ± 7% (control)/n = 7]. By contrast, combination of cyclosporin and clopidogrel compared with clopidogrel alone showed no additive effect. These results demonstrate that combination of platelet- and mammalian target of Rapamycin-inhibition can dramatically reduce the development of transplant arteriosclerosis. © 2010 The Authors.
CRIS-Team Scopus Importer:2024-06-04
Keywords: clopidogrel; mammalian target of rapamycin inhibitor; platelets; transplant arteriosclerosis

Combined free flaps with arteriovenous loops for reconstruction of extensive thoracic defects after sternal osteomyelitis - Taeger, Christian; Horch, Raymund E.; Arkudas, Andreas; Schmitz, Marweh; Stübinger, Axel; Lang, Werner; Meyer, Alexander; Seitz, Tatjana; Weyand, Michael; Beier, Justus (Microsurgery, 2016)
Various local flaps have been described for patients suffering from sternal osteomyelitis and are regarded as a standard procedure for defect reconstruction. In contrast, the use of microsurgical free flaps has been reported anecdotally only. We present our experiences with the combination of an arteriovenous loop and a free flap transfer in defects larger than half of the sternum.Between January 2012 and October 2014, eight patients with a mean age of 68 years who suffered from extensive deep sternal osteomyelitis were operated in a consecutive series. After radical surgical debridement, the defect size comprised all three thirds of the sternum. Defect reconstruction was achieved by means of free flap transplantation using the vastus lateralis myocutaneous flap, rectus abdominis, and bipedicled latissimus dorsi/parascapular flap. As local recipient vessels were depleted in all patients, the pedicle of the flap was anastomosed to a high-flow and short-length subclavian arteriovenous loop as recipient vessel in all cases.The immediate postoperative course in all patients was uneventful despite one axonal injury to the femoral nerve at the donor site. There was no partial or total flap loss. During a mean follow-up of 9 months, one patient suffered from a local infection at the donor site. In all patients, a successful defect reconstruction could be achieved.Depletion of local recipient vessels as an obstacle for free flap reconstruction can be overcome by creating an arteriovenous loop. Even extensive defects are adequate for defect reconstruction using a single or, in extreme cases, bipedicled free flap. © 2015 Wiley Periodicals, Inc. Microsurgery 36:121-127, 2016.
EVALuna2:15222

Comparative Study of 2D-Cine and 3D-wh Volumetry: Revealing Systemic Error of 2D-Cine Volumetry - Alkassar, Muhnnad; Engelhardt, Sophia; Abu-Tair, Tariq; Ojeda, Efren; Treffer, Philipp C.; Weyand, Michael; Rompel, Oliver (Diagnostics, 2023)
This study investigates the crucial factors influencing the end-systolic and end-diastolic volumes in MRI volumetry and their direct effects on the derived functional parameters. Through the simultaneous acquisition of 2D-cine and 3D whole-heart slices in end-diastole and end-systole, we present a novel direct comparison of the volumetric measurements from both methods. A prospective study was conducted with 18 healthy participants. Both 2D-cine and 3D whole-heart sequences were obtained. Despite the differences in the creation of 3D volumes and trigger points, the impact on the LV volume was minimal (134.9 mL ± 16.9 mL vs. 136.6 mL ± 16.6 mL, p < 0.01 for end-diastole; 50.6 mL ± 11.0 mL vs. 51.6 mL ± 11.2 mL, p = 0.03 for end-systole). In our healthy patient cohort, a systematic underestimation of the end-systolic volume resulted in a significant overestimation of the SV (5.6 mL ± 2.6 mL, p < 0.01). The functional calculations from the 3D whole-heart method proved to be highly accurate and correlated well with function measurements from the phase-contrast sequences. Our study is the first to demonstrate the superiority of 3D whole-heart volumetry over 2D-cine volumetry and sheds light on the systematic error inherent in 2D-cine measurements.
CRIS-Team Scopus Importer:2023-11-10
Keywords: 2D-cine MRI; 3D-wh MRI; cardiac volumetry

Comparison of Plasma and Urine Biomarker Performance in Acute Kidney Injury - Schley, Gunnar; Köberle, Carmen; Manuilova, Ekaterina; Rutz, Sandra; Forster, Christian; Weyand, Michael; Formentini, Ivan; Kientsch-Engel, Rosemarie; Eckardt, Kai-Uwe; Willam, Carsten (PLoS ONE, 2015)
New renal biomarkers measured in urine promise to increase specificity for risk stratification and early diagnosis of acute kidney injury (AKI) but concomitantly may be altered by urine concentration effects and chronic renal insufficiency. This study therefore directly compared the performance of AKI biomarkers in urine and plasma.This single-center, prospective cohort study included 110 unselected adults undergoing cardiac surgery with cardiopulmonary bypass between 2009 and 2010. Plasma and/or urine concentrations of creatinine, cystatin C, neutrophil gelatinase-associated lipocalin (NGAL), liver fatty acid-binding protein (L-FABP), kidney injury molecule 1 (KIM1), and albumin as well as 15 additional biomarkers in plasma and urine were measured during the perioperative period. The primary outcome was AKI defined by AKIN serum creatinine criteria within 72 hours after surgery.Biomarkers in plasma showed markedly better discriminative performance for preoperative risk stratification and early postoperative (within 24h after surgery) detection of AKI than urine biomarkers. Discriminative power of urine biomarkers improved when concentrations were normalized to urinary creatinine, but urine biomarkers had still lower AUC values than plasma biomarkers. Best diagnostic performance 4h after surgery had plasma NGAL (AUC 0.83), cystatin C (0.76), MIG (0.74), and L-FAPB (0.73). Combinations of multiple biomarkers did not improve their diagnostic power. Preoperative clinical scoring systems (EuroSCORE and Cleveland Clinic Foundation Score) predicted the risk for AKI (AUC 0.76 and 0.71) and were not inferior to biomarkers. Preexisting chronic kidney disease limited the diagnostic performance of both plasma and urine biomarkers.In our cohort plasma biomarkers had higher discriminative power for risk stratification and early diagnosis of AKI than urine biomarkers. For preoperative risk stratification of AKI clinical models showed similar discriminative performance to biomarkers. The discriminative performance of both plasma and urine biomarkers was reduced by preexisting chronic kidney disease.
EVALuna2:3825

Congenital heart disease – don't forget the aorta Angeborene Herzfehler – die Aorta nicht vergessen - Huntgeburth, Michael; Kaemmerer, Ann-Sophie; Meierhofer, C.; Freilinger, S.; Weyand, Michael; Ewert, P.; von Kodolitsch, Y. (Chirurgische Praxis, 2023)
Patients with congenital heart disease (CHD) are considered chronically ill. Despite the growing body of evidence for the relevance of aortic disease in the context of CHD, it is vastly neglected. An aortopathy can have a major negative impact on morbidity and mortality, depending on the underlying heart defect and the patient’s age. Therefore, all affected patients require a life-long follow-up and access to state-of-the art specialized care. Future goals consequently aim to an increased awareness both in caregivers and patients for aortic affections and complications in patients with CHD.
CRIS-Team Scopus Importer:2023-10-20
Keywords: aortic aneurysm; aortic dilatation; aortopathy; congenital heart disease; connective tissue disease; hereditary aortic disease

Continuous Long-Term Assessment of Heart Rate Variability in Adults with Cyanotic Congenital Heart Disease after Surgical Repair - Pieringer, Felix; Suleiman, Mathieu; Kaemmerer-Suleiman, Ann-Sophie; Dewald, Oliver; Freiberger, Annika; Huntgeburth, Michael; Nagdyman, Nicole; Neidenbach, Rhoia; von Scheidt, Fabian; Kaemmerer, Harald; Ewert, Peter; Weyand, Michael; et al. (Journal of Clinical Medicine, 2024)
Background: Heart rate variability (HRV) is an established, non-invasive parameter for the assessment of cardiac autonomic nervous activity and the health status in general cardiology. However, there are few studies on HRV in adults with congenital heart defects (CHDs). The aim of the present study was to evaluate the use of long-term continuous HRV measurement for the assessment of global health status in adults with cyanotic CHD. Methods: This prospective study included 45 adults (40% female, mean age = 35.2 ± 9.2 [range: 19–58] years) after cardiac surgical repair. HRV parameters were calculated from continuous 24 h measurements using a Bittium Faros 180 sensor (Bittium Corp., Oulu, Finland). Results: Postoperative patients with transposition of the great arteries (TGA) (n = 18) achieved significantly higher values of standard deviation of NN intervals (SDNN) (175.4 ± 59.9 ms vs. 133.5 ± 40.6 ms; p = 0.013) compared with patients with other conotruncal anomalies (n = 22). Comparing patients with TGA after a Senning–Brom or Mustard operation (n = 13) with all other heart surgery patients (n = 32), significantly higher HRV parameters were found after atrial switch (root mean square of successive RR interval differences: 53.6 ± 20.7 ms vs. 38.4 ± 18.3 ms; p = 0.019; SDNN: 183.5 ± 58.4 ms vs. 136.3 ± 45.3 ms; p = 0.006). A higher SDNN was also measured after Senning–Brom or Mustard operations than after a Rastelli operations (n = 2) (SDNN: 183.5 ± 58.4 ms vs. 84.5 ± 5.2 ms; p = 0.037). When comparing atrial switch operations (n = 3) with Rastelli operations, the SDNN value was significantly shorter in the Rastelli group (p = 0.004). Conclusions: Our results suggest that continuous HRV monitoring may serve as a marker of cardiac autonomic dysfunction in adults with cyanotic CHD after surgical repair. Impaired cardiac autonomic nervous activity may be associated with an increased risk of adverse reactions in patients with repaired CHD. Therefore, a longitudinal assessment of HRV patterns and trends may provide a deeper insight into dynamic changes in their autonomic regulation and disease progression, lifestyle changes, or treatments. As each person has individual variability in heart rate, HRV may be useful in assessing intra-individual disease progression and may help to improve personalized medicine. Further studies are needed to better understand the underlying mechanisms and to explore the full potential of HRV analysis to optimize medical care for ACHDs.
CRIS-Team Scopus Importer:2024-04-19
Keywords: ACHD; adults with congenital heart disease; arterial switch; atrial switch; cardiac surgery; complete transposition of the great arteries; cyanotic congenital heart defects; heart rate variability; Rastelli operation

Correction: Patient-tailored silicone plug for HeartMate 3™ left ventricular assist device explantation (Journal of Artificial Organs, (2023), 10.1007/s10047-023-01397-w) - Elbayomi, Mohamed; Tandler, Rene; Ebel, Nina; Schubert, Dirk W.; Werner, Siegfried; Kondruweit, Markus; Weyand, Michael; Heim, Christian (Journal of Artificial Organs, 2023)
In this article the author’s name Dirk W. Schubert was incorrectly written as Shubert Dirk. Also, the given and family names of the authors were incorrectly structured. The correct name should read as “Mohamed Elbayomi, Rene Tandler, Nina Ebel, Dirk W. Schubert, Siegfried Werner, Markus Kondruweit, Micheal Weyand, Christian Heim". The original article has been corrected.
CRIS-Team Scopus Importer:2023-12-08

Corrigendum: long-term cultivation of human atrial myocardium (Frontiers in Physiology, (2022), 13, (839139), 10.3389/fphys.2022.839139) - Klumm, Maximilian J. J.; Heim, Christian; Fiegle, Dominik; Weyand, Michael; Volk, Tilmann; Seidel, Thomas (Frontiers in Physiology, 2023)
In the published article, there was an error in Author Contributions. The following sentence was missing. MK performed this work in (partial) fulfillment of the requirements for obtaining the degree “Dr. med.”. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2023-06-02
Keywords: calcium imaging; confocal microscopy; gene expression; human atrium; in vitro; refractory period; tissue culture

CT predictors of post-procedural aortic regurgitation in patients referred for transcatheter aortic valve implantation: An analysis of 105 patients - Marwan, Mohamed; Achenbach, Stephan; Ensminger, Stefan M.; Pflederer, Tobias; Ropers, Dieter; Ludwig, Josef; Weyand, Michael; Daniel, Werner; Arnold, Martin (International Journal of Cardiovascular Imaging, 2013)
Cardiac computed tomography (CT) allows accurate and detailed analysis of the anatomy of the aortic root and valve, including quantification of calcium. We evaluated the correlation between different CT parameters and the degree of post-procedural aortic regurgitation (AR) after transcatheter aortic valve implantation (TAVI) using the balloon-expandable Edwards Sapien prosthesis. Preintervention contrast-enhanced dual source CT data sets of 105 consecutive patients (48 males, mean age 81 ± 6 years, mean logEuroSCORE 34 ± 13 %) with symptomatic severe aortic valve stenosis referred for TAVI using the Edwards Sapien prosthesis (Edwards lifesciences, Inc., CA, USA) were analysed. The degrees of aortic valve commissural calcification and annular calcification were visually assessed on a scale from 0 to 3. Furthermore, the degree of aortic valve calcification as quantified by the Agatston score, aortic annulus eccentricity, aortic diameter at the level of the sinus of valsalva and at the sinotubular junction were assessed. Early post-procedural AR was assessed using aortography. Significant AR was defined as angiographic AR of at least moderate degree (AR ≥ 2). Visual assessment of the degree of aortic annular calcification as well as the Agatston score of aortic valve calcium correlated weakly, yet significantly with the degree of post-procedural AR (r = 0.31 and 0.24, p = 0.001 and 0.013, respectively). Compared to patients with AR<2, patients with AR ≥ 2 showed more severe calcification of the aortic annulus (mean visual scores 1.9 ± 0.6 vs. 1.5 ± 0.6, p = 0.003) as well as higher aortic valve Agatston scores (1,517 ± 861 vs. 1,062 ± 688, p = 0.005). Visual score for commissural calcification did not differ significantly between both groups (mean scores 2.4 ± 0.5 vs. 2.5 ± 0.5, respectively, p = 0.117). No significant correlation was observed between the degree of AR and commissural calcification, aortic annulus eccentricity index or aortic diameters. The extent of aortic valve annular calcification, but not of commissural calcification, predicts significant post-procedural AR in patients referred for TAVI using the balloon-expandable Edwards Sapiens prosthesis.
CRIS-Team Scopus Importer:2023-03-08
Keywords: AR; CT; TAVI

Cytomegalovirus chemokine receptor M33 knockout reduces chronic allograft rejection in a murine aortic transplant model - Fritz, Niklas; Stamminger, Thomas; Ramsperger-Gleixner, Martina; Kuckhahn, Annika V.; Müller, Regina; Weyand, Michael; Heim, Christian (Transplant Immunology, 2021)
Background: Numerous studies suggest that cytomegalovirus (CMV) infection may act as isolated risk factor in the development of cardiac allograft vasculopathy (CAV). Viral G protein-coupled receptors (GPCRs) are thought to contribute to the pathogenic changes associated with CMV infection. The aim of this study was to investigate the role of murine cytomegalovirus GPCR M33 in the development of CAV in a murine aortic allograft model. Methods: MHC I-mismatched aortas of C.B10 (H2b) mice were transplanted into BALB/c (H2d) recipients, which were either mock-infected, infected with wild type (WT) MCMV or MCMV with a deleted M33-receptor gene (delM33). Persistence of cytomegalovirus infection was confirmed by qPCR and by luciferase assay to ensure active viral replication. Grafts were harvested on days 21 and 37 for intragraft mRNA expression and histological analysis. Results: Active viral replication was demonstrated and MCMV presence was confirmed by PCR within spleen, liver, salivary glands, lung and the aortic transplant. Infection with delM33 resulted in significantly less intimal proliferation compared to WT-MCMV but more pronounced proliferation than in mock-infected allografts (32.19% [delM33] vs. 41.71% [WT-MCMV] vs. 24.33% [MCMV-]). Intragraft expression of most analyzed genes was significantly increased in infected mice. VCAM-1, ICAM-1, PDGFβ, CXCR3 and Granzyme B were distinctly less expressed in grafts of delM33 infected compared to WT infected mice. Cellular infiltration revealed reduced dendritic cells and T cells in grafts infected with delM33 compared to WT MCMV. Conclusions: These data suggest that the MCMV encoded receptor M33 plays an important role as a viral effector mechanism contributing to the development of CAV in a murine aortic transplant model.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Cardiac allograft vasculopathy; CAV; Chemokine receptor; M33; Murine cytomegalovirus; US28

Cytomegalovirus Donor Seropositivity Negatively Affects Survival After Heart Transplantation - Heim, Christian; Müller, Philipp; Tandler, Rene; Cherikh, Wida S.; Toll, Alice E.; Stehlik, Josef; Weyand, Michael; Khush, Kiran K.; Ensminger, Stephan M. (Transplantation, 2022)
Background. Prior studies have shown that cytomegalovirus (CMV) infection is a risk factor for the development of cardiac allograft vasculopathy (CAV) and is associated with reduced long-term survival after heart transplantation (HTx). The aim of this International Society for Heart and Lung Transplantation Transplant Registry study was to compare posttransplant survival in different CMV donor:recipient serologic combinations. Methods. We performed a retrospective cohort study, using the International Society for Heart and Lung Transplantation Thoracic Transplant Registry, on 15 885 adult primary heart transplant recipients with known CMV serologic status between July 2004 and June 2014. Posttransplant survival and risk of developing CAV were compared across 4 groups: CMV-seronegative recipients (R-) receiving CMV-positive grafts (D+), intermediate-risk patients (D+R+ and D-R+), and low-risk patients (D-R-). Results. Baseline characteristics (donor/recipient age, body mass index, recipient serum creatinine, blood group, donor cause of death, recipient diagnosis, and ischemic time) were mostly balanced between the groups. Kaplan-Meier survival analyses over a follow-up of 10 y revealed significantly worse survival for both D+ groups as compared to the CMV low-risk group (D+R+: 56.61% [95% confidence interval, 53.94-59.41] versus D-R-: 63.09% [59.74-66.64] P < 0.01 and D+R-: 57.69% [56.03-59.39] versus D-R-; P < 0.001), whereas recipient seropositivity alone was not associated with reduced survival (D-R+ versus D-R- P = 0.178). The risk of developing CAV after HTx was not significantly increased in D+ as compared to D- groups. Conclusions. In a large contemporary cohort, CMV status at the time of HTx was not associated with CAV development. However, there was a significant association between donor CMV seropositivity and reduced short- and long-term survival after HTx. Approaches to mitigate the impact of CMV on posttransplant survival are needed.
CRIS-Team WoS Importer:2022-06-10

Delayed therapy with clopidogrel and everolimus prevents progression of transplant arteriosclerosis and impairs humoral alloimmunity in murine aortic allografts - Heim, Christian; Eckl, Sebastian; Preidl, Raimund; Ramsperger-Gleixner, Martina; Koch, Nina; Goldmann, Katja; Spriewald, Bernd M.; Weyand, Michael; Ensminger, Stephan M. (European Journal of Cardio-Thoracic Surgery, 2015)
It was previously shown that the combination of clopidogrel and everolimus reduced the development of transplant arteriosclerosis. The aim of this study was to investigate whether delayed onset of treatment, similar to the clinical situation after heart transplantation, inhibits progression of transplant arteriosclerosis.Fully allogeneic C57BL/6 (H2-b) donor aortas were transplanted into CBA.J (H2-k) recipients treated with clopidogrel and everolimus alone or in combination starting on Days 1, 7 or 14. Grafts were analysed by histology and alloantibodies were detected by fluorescence activated cell sorting after transplantation.Delayed platelet inhibition with clopidogrel reduced the development of transplant arteriosclerosis [neointima formation (Day 14): 50 ± 4 vs 84 ± 9% (control)]. The combination of clopidogrel and everolimus almost abolished formation of transplant arteriosclerosis when therapy was started on Day 1 [neointima formation (Day 1): 14 ± 5 vs 84 ± 9% (control)] and also showed a remarkable reduction in both delayed treatment groups [neointima formation (Day 7): 24 ± 7 vs 84 ± 9% (control); neointima formation (Day 14): 28 ± 11 vs 84 ± 9% (control)]. Platelet inhibition alone and in combination with everolimus resulted in reduced alloantibody production.These results demonstrate that delayed treatment with clopidogrel and everolimus-representative of a clinical setting-prevents the progression of transplant arteriosclerosis and impairs humoral immunity in this experimental model.
EVALuna2:16087

Destination Therapy with the magnetically levitated HVAD - Heim, Christian; Rösch, Johannes; Zielezinski, Thorsten; Ballazhi, Fatos; Kondruweit, Markus; Weyand, Michael; Tandler, Rene (Journal of Cardiothoracic Surgery, 2015)
EVALuna2:16105

Developing a patient individualized flexible silicone implant using SLS and vacuum die casting - Launhardt, Martin; Ebel, Nina; Kondruweit, Markus; Weyand, Michael; Volk, Tilmann; Drummer, Dietmar (AIP Conference Proceedings, 2019)

Development of a new sternal dehiscence prediction scale for decision making in sternal closure techniques after cardiac surgery - Nooh, Ehab; Griesbach, Colin; Rösch, Johannes; Weyand, Michael; Harig, Frank (Journal of Cardiothoracic Surgery, 2021)
Background: After sternotomy, the spectrum for sternal osteosynthesis comprises standard wiring and more complex techniques, like titanium plating. The aim of this study is to develop a predictive risk score that evaluates the risk of sternum instability individually. The surgeon may then choose an appropriate sternal osteosynthesis technique that is risk- adjusted as well as cost-effective. Methods: Data from 7.173 patients operated via sternotomy for all cardiovascular indications from 2008 until 2017 were retrospectively analyzed. Sternal dehiscence occurred in 2.5% of patients (n = 176). A multivariable analysis model examined pre- and intraoperative factors. A multivariable logistic regression model and a backward elimination based on the Akaike Information Criterion (AIC) a logistic model were selected. Results: The model showed good sensitivity and specificity (area under the receiver-operating characteristic curve, AUC: 0.76) and several predictors of sternal instability could be evaluated. Multivariable logistic regression showed the highest Odds Ratios (OR) for reexploration (OR 6.6, confidence interval, CI [4.5–9.5], p < 0.001), obesity (body mass index, BMI > 35 kg/m2) (OR 4.23, [CI 2.4–7.3], p < 0.001), insulin-dependent diabetes mellitus (IDDM) (OR 2.2, CI [1.5–3.2], p = 0.01), smoking (OR 2.03, [CI 1.3–3.08], p = 0.001). After weighting the probability of sternum dehiscence with each factor, a risk score model was proposed scaling from − 1 to 5 points. This resulted in a risk score ranging up to 18 points, with an estimated risk for sternum complication up to 74%. Conclusions: A weighted scoring system based on individual risk factors was specifically created to predict sternal dehiscence. High-scoring patients should receive additive closure techniques.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Cardiac surgery; Prediction; Scoring system; Sternal dehiscence; Tailored technique

Die unterschätzte Rolle von Thrombozyten bei der Herztransplantation. The underestimated role of platelets in heart Transplantation. - Heim, Christian; Eckl, Sebastian; Weyand, Michael; Ensminger, Stephan; et al. (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2010)

Direct Impact of Human Platelets on the Development of Transplant Arteriosclerosis. - Görner, Susann; Heim, Christian; Weigmann, Benno; Von Silva-Tarouca, Benjamin; Kuckhahn, Annika; Ramsperger-Gleixner, Martina; Zimmermann, Robert; Weyand, Michael; Ensminger, Stephan M. (Transplantation, 2022)
BACKGROUND: Platelets play an important role in the pathogenesis of inflammatory and proliferative vascular changes. The aim of this study was to investigate whether human platelets are able to induce transplant arteriosclerosis in a humanized C57/Bl6-Rag2-/-γc-/- mouse xenograft model. METHODS: Nonactivated and in vitro-activated human platelets were analyzed and phenotyped for surface markers by flow cytometry. Side branches of human mammary arteries were implanted into the infrarenal aorta of recipients, followed by daily application of human platelets and histological analyzed on day 30 after transplantation. RESULTS: Human platelets collected by apheresis had low levels of platelet activation markers. However, after in vitro activation, expression was markedly increased. Sixty minutes after injection in recipient mice, nonactivated human platelets become significantly activated. Increased adhesion of platelets to the vascular endothelium was detected by in vivo fluorescence microscopy. After intravenous injection of nonactivated or activated platelets, human xenografts showed pronounced intimal proliferation. Immunohistological analysis showed that the group treated with activated human platelets exhibited significantly increased intragraft protein expression of intracellular adhesion molecule-1 and platelet-derived growth factor receptor beta and smooth muscle cell migration into the neointima. CONCLUSIONS: These data demonstrate that an isolated daily application of both in vivo- and in vitro-activated human platelets results in the development of transplant arteriosclerosis in a humanized mouse transplantation model.
EVALuna2:473994

DJ1 and microRNA-214 act synergistically to rescue myoblast cells after ischemia/reperfusion injury - Ghaderi, Shahrooz; Alidadiani, Neda; Soleimanirad, Jafar; Heidari, Hamid R.; Dilaver, Nafi; Heim, Christian; Ramsperger-Gleixner, Martina; Baradaran, Behzad; Weyand, Michael (Journal of Cellular Biochemistry, 2018)
Ischemia/reperfusion injury is a tissue injury occurring post-reperfusion of tissues with pre-existing ischemia. A good blood supply to tissues aids in the survival of ischemic tissue, however, due to prolonged ischemia the levels of ATP decrease and pH declines leading to acidosis. Reduced ATP leads to an increase in the AMP/ATP ratio, causing cessation of intracellular calcium transport, hence calcium overload and cell death. In this study, we demonstrate the synergistic and antagonistic effect of DJ1 and microR-214 (miR-214) in rescuing myoblast C2C12 cells after ischemia/reperfusion in an in vitro model. Both DJ1 and miR-214 were cloned into a hypoxic inducible expression cassette and transfected into the C2C12 cells. We showed that DJ1 and miR-214 have synergistic effects in reducing intracellular lactate dehydrogenase and intracellular transient calcium levels after reoxygenation compared to control cells, in addition to reducing cell death via necrosis. Western blotting revealed a decrease in autophagosome formation in LC3II/I ratio and an increase in AKT expression in cells transfected with DJ1 and miR-214. Using quantitative real-time PCR, we demonstrated that DJ1 and miR-214 significantly reduced the expression of pro-apoptotic factors and autophagy compared to control. The results indicated DJ1 is an endogenous oxidative stress molecule and miR-214 is a potent inhibitor of the sodium calcium exchanger channel. DJ1 had the greatest effect to inhibiting mitochondrial cell death pathways by possibly acting as a modulator of autophagy. Additionally, we have concluded that miR-214 has an inhibitory effect on extrinsic cell death pathways such as necrosis and autophagy.
EVALuna2:215375

Double valve replacement in a case of Hedinger syndrome - Pathare, Presheet; Weyand, Michael; Heim, Christian (Clinical Case Reports, 2023)
Hedinger Syndrome or carcinoid heart disease is a rare cardiac complication of neuroendocrine tumors (NET) affecting the tricuspid and pulmonary valves. Following is a case description of a patient undergoing treatment for a neuroendocrine tumor with liver metastasis, referred with symptomatic tricuspid valve regurgitation and pulmonary valve stenosis for surgical valve replacement. Planned surgical valve replacement was successfully performed before the onset of severe right ventricular failure or pulmonary hypertension in this case of carcinoid heart disease. An interdisciplinary approach and regular follow up is recommended in such cases.
CRIS-Team WoS Importer:2023-02-03

Dysphonia as a Presenting Symptom of a Giant Left Atrial Sarcoma Developing within Five Years - Elbayomi, Mohamed; Nooh, Ehab; Weyand, Michael; Agaimy, Abbas; Harig, Frank (Thoracic and Cardiovascular Surgeon Reports, 2022)
An 83-year-old woman presented with a new onset of dyspnea and dysphonia. Physical examination revealed no abnormalities. Computerized tomography, bidimensional echocardiography, and cardiac magnetic resonance confirmed the presence of a cardiac mass in the left atrium. Surgical resection was uneventful and showed the origin of the mass in the ostium of the left inferior pulmonary vein. Histological evaluation revealed undifferentiated pleomorphic sarcoma with myxoid features. This case highlights the importance of considering cardiac neoplasms as a rare differential diagnosis, including rare and misleading clinical presentations.
CRIS-Team WoS Importer:2022-09-02

Effects of different serotonin receptor subtype antagonists on the development of cardiac allograft vasculopathy in murine aortic allografts - Gocht, Annika; Distler, Jörg; Spriewald, Bernd; Ramsperger-Gleixner, Martina; Weyand, Michael; Ensminger, Stephan M.; Heim, Christian (Transplant Immunology, 2018)
BACKGROUND: Cardiac allograft vasculopathy (CAV) is the main obstacle for long-term survival after heart transplantation. Alloimmune mediated chronic vascular rejection results in several mechanisms like platelet activation, immigration of inflammatory cells through the endothelial layer and proliferation and migration of smooth muscle cells (SMCs). Serotonin (5-HT) promotes these processes via activation of 5-HT2 receptors. We hypothesized that inhibiting 5-HT2 receptors ameliorates the development of CAV. METHODS: CBA/JRj mice recieved aortic grafts from C57BL/6 mice. After transplantation until recovery of organs, recipients were treated with serotonin receptor antagonists: sarpogrelate (5-HT2A), SB 204741 (5-HT2B) or terguride (5-HT2A+B). Mice were sacrificed after 14 days for qRT-PCR analysis or after 30 days for histological evaluation. Serum serotonin ELISA was done at both time points. RESULTS: Elevated serum serotonin levels were significantly reduced after 5-HT2A antagonist treatment as was 5-HT2A receptor expression. This went along with reduced inflammation characterized by significantly fewer infiltrating macrophages and pro-inflammatory intragraft cytokines and with reduced tissue remodeling evident as significantly less neointima formation. CONCLUSION: Inhibition of the 5HT/5-HT2A receptor axis leads to significantly reduced neointima proliferation after aortic transplantation associated with reduced transendothelial migration of macrophages and decreased expression of inflammatory cytokines. These findings have translational implications as inhibitors of 5HT2A like sarpogrelate are already approved for clinical use.
EVALuna2:35106

EFFICACY OF WNT PATHWAY INHIBITORS FOR THE PREVENTION OF CARDIAC ALLOGRAFT VASCULOPATHY IN A MOUSE MODEL - Kuckhahn, A.; Ramsperger-Gleixner, Martina; Distler, Jörg; Spriewald, B.; Ensminger, S.; Weyand, Michael; Heim, Christian (TRANSPLANT INTERNATIONAL, 2019)
CRIS-Team WoS Importer:2019-10-29

Endovascular stenting of an HVAD (TM) outflow graft pseudoaneurysm that exerts compression and kinking stenosis on the soft portion of the prosthesis - Elbayomi, Mohamed; Weyand, Michael; Uder, Michael; May, Matthias; Steger, Katrin; Roth, Jan-Peter; Tandler, Rene (Clinical Case Reports, 2023)
Key Clinical MessageComplex presentations of MCS patients may necessitate a multidisciplinary approach involving HF cardiologists, CT surgeons, advanced cardiac imagers, and interventional cardiologists in order to define the optimal management strategy. Left ventricle assist devices (LVADs) provide life-sustaining treatment for patients with terminal heart failure, but their intricacy allows for complications. One complication is LVAD outflow graft obstruction due to the graft's intraluminal thrombus or extraluminal compression. It may be treated endovascularly with stenting. We report an endovascular stenting of an outflow tract in HVAD (TM) (HeartWare Inc.) due to a pseudoaneurysm causing compression and kinking stenosis.
CRIS-Team WoS Importer:2023-06-02

„Erwachsene mit angeborenen Herzfehlern“: Aktuelle Herausforderung in der medizinischen Versorgung Teil I: Versorgungsstruktur und Problematik, Herzinsuffizienz, Herzrhythmusstörungen: Positionspapier der Deutschen Gesellschaft für Kardiologie - Kaemmerer, Harald; Baldus, Stephan; Baumgartner, Helmut; Berger, Felix; de Haan, Fokko; Frantz, Stefan; Loßnitzer, Dirk; Uebing, Anselm; Lebherz, Corinna; Weyand, Michael; Diller, Gerhard Paul (Die Kardiologie, 2023)
Nowadays, most patients with congenital heart defects (CHD) survive into adulthood. Unfortunately, despite relevant residuals and sequelae, follow-up of adults with congenital heart defects (ACHD) is predominantly performed by nonspecialized physicians or hospitals with little experience in the field of ACHD. Major problems in the long-term course include CHD-related residua, heart failure, cardiac arrhythmia, valvular heart disease, pulmonary vascular disease/pulmonary hypertension, infective endocarditis and aortopathy, as well as cardiac and noncardiac comorbidities. Many problems in ACHD manifest differently from those of acquired heart disease, and treatment regimens from general cardiology cannot be directly applied to CHD. It should be noted that even simple postoperative cardiac defects, which until recently were considered harmless, can develop serious CHD-related complications with advancing age, a fact that was rarely anticipated. Therefore, the treatment of ACHD has many special features and requires special expertise. This position paper of the German Cardiac Society provides a highly up to date overview and highlights current data on epidemiology, heart failure, and cardiac arrhythmias in ACHD.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Adults; Cardiac arrhythmias; Congenital heart disease; Follow-up; Heart failure; Structure of care

ESC-leitlinienbasierte Therapieempfehlungen für herzinsuffiziente Patienten in der Herzchirurgie - Heim, Christian; Tandler, Rene; Weyand, Michael (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2018)
Background: Heart failure is a common and potentially fatal condition with increasing numbers of patients suffering from chronic heart failure. Current national and European guidelines include surgical options for the treatment of congestive heart failure. Objective: The aim of this article is to provide physicians actively involved in cardiac surgery with a practice-related overview of guideline-based treatment approaches for heart insufficiency. Material and methods: The current guidelines of the European Society of Cardiology (ESC) were utilized as the foundations of this review article and those topics which are relevant for cardiac surgery practice were elaborated. Results: Principally, indications for an operative approach for heart insufficiency can be either symptomatic or from a prognostic perspective. Electrophysiological devices can prolong life by a prophylactic application and relieve symptoms of heart insufficiency by a rhythmological application. High-risk bypass operations, if necessary in combination with geometric ventricular corrective surgery can also prolong life and reduce the symptoms. Valvular diseases can be the cause and consequence of heart failure. Aortic valve replacement in high-grade diseases as well as mitral valve surgery for functional mitral valve insufficiency can be treated by guideline-conform surgery. In patients with end-stage heart failure heart transplantation or implantation of ventricular assist devices (VAD) can improve the quality of life and prolong life. Conclusion: Generally, patients with heart failure should always receive interdisciplinary treatment, if possible in centers which can provide specialized cardiac surgery.
CRIS-Team Scopus Importer:2024-06-04
Keywords: Cardiac resynchronization pacing therapy; Coronary artery bypass grafting; Heart failure; Heart transplantation; Implantable cardioverter-defibrillators; Ventricular assist device

Facts about the General Medical Care of Adults with Congenital Heart Defects: Experience of a Tertiary Care Center - Seidel, Lavinia; Nebel, Kathrin; Achenbach, Stephan; Bauer, Ulrike; Ewert, Peter; Freilinger, Sebastian; Gundlach, Ulrike; Kaemmerer, Harald; Nagdyman, Nicole; Oberhoffer, Renate; Pieper, Lars; Reinhard, Wibke; et al. (Journal of Clinical Medicine, 2020)
Background: Due to the increase in survival rates for congenital heart disease (CHD) in the last decades, over 90% of patients today reach adulthood. Currently, there are more than 300,000 adults with CHD (ACHD) living in Germany. They have an increased need for specialized medical care, since almost all ACHD have chronic heart disease and suffer from specific chronic symptoms, risks, and sequelae. Primary care physicians (PCPs) play a crucial role in referring patients to ACHD specialists or specialized institutions. This cross-sectional study is intended to clarify the real-world care of ACHD from the PCP's perspective.Methods:This analysis, initiated by the German Heart Centre Munich, was based on a 27-item questionnaire on actual ACHD health care practice in Germany from the PCP's perspective.Results: In total, 767 questionnaires were considered valid for inclusion. The majority of the PCPs were general practitioners (95.9%), and 84.1% had cared for ACHD during the past year. A majority (69.2%) of the PCPs had cared for patients with simple CHD, while 50.6% and 33.4% had cared for patients with moderate and severe CHD, respectively, in all age groups. PCPs treated almost all typical residual symptoms and sequelae, and advised patients regarding difficult questions, including exercise capacity, pregnancy, genetics, and insurance matters. However, 33.8% of the PCPs did not even know about the existence of certified ACHD specialists or centers. Only 23.9% involved an ACHD-specialized physician in their treatment. In cases of severe cardiac issues, 70.8% of the PCPs referred patients to ACHD-certified centers. Although 52.5% of the PCPs were not sufficiently informed about existing structures, 64.2% rated the current care situation as either "very good" or "good". Only 26.3% (n= 190) of the responding physicians were aware of patient organizations for ACHD.Conclusions: The present study showed that the majority of PCPs are not informed about the ACHD care structures available in Germany. The need for specialized ACHD follow-up care is largely underestimated, with an urgent need for optimization to reduce morbidity and mortality. For the future, solutions must be developed to integrate PCPs more intensively into the ACHD care network.
CRIS-Team WoS Importer:2020-07-31

Familial acute aortic dissection associated with a novel ACTA2 germline variant - Strecker, Thomas; Wiesmueller, Felix; Rudnik-Schoeneborn, Sabine; Hoyer, Juliane; Wiesmann da Silva Reis, André; Weyand, Michael; Agaimy, Abbas (Virchows Archiv, 2022)
Aortic dissection is a life-threatening cardiovascular disease. Hereditary disorders are responsible for a small percentage of cases. Nonetheless, it is important to identify genetic causes, as they are often autosomal dominantly inherited and are of life-saving importance if we can identify persons at risk. Mutations of the ACTA2 gene are the most common cause of non-syndromic familial aortic disease. Exploration of the genetic background in suspected familial cases and determination of the exact etiology are mandatory for management and establishing appropriate follow-up strategies due to the risk of fatal recurrences. Herein, we present a 21-year-old male with a familial acute aortic dissection associated with novel ACTA2 germline variant and discuss the management and surveillance considerations.
CRIS-Team WoS Importer:2022-08-05

Glucocorticoids preserve the t-tubular system in ventricular cardiomyocytes by upregulation of autophagic flux - Seidel, Thomas; Fiegle, Dominik; Baur, Tim J.; Ritzer, Anne; Nay, Sandra; Heim, Christian; Weyand, Michael; Milting, Hendrik; Oakley, Robert H.; Cidlowski, John A.; Volk, Tilmann (Basic Research in Cardiology, 2019)
A major contributor to contractile dysfunction in heart failure is remodelling and loss of the cardiomyocyte transverse tubular system (t-system), but underlying mechanisms and signalling pathways remain elusive. It has been shown that dexamethasone promotes t-tubule development in stem cell-derived cardiomyocytes and that cardiomyocyte-specific glucocorticoid receptor (GR) knockout (GRKO) leads to heart failure. Here, we studied if the t-system is altered in GRKO hearts and if GR signalling is required for t-system preservation in adult cardiomyocytes. Confocal and 3D STED microscopy of myocardium from cardiomyocyte-specific GRKO mice revealed decreased t-system density and increased distances between ryanodine receptors (RyR) and L-type Ca2+ channels (LTCC). Because t-system remodelling and heart failure are intertwined, we investigated the underlying mechanisms in vitro. Ventricular cardiomyocytes from failing human and healthy adult rat hearts cultured in the absence of glucocorticoids (CTRL) showed distinctively lower t-system density than cells treated with dexamethasone (EC50 1.1 nM) or corticosterone. The GR antagonist mifepristone abrogated the effect of dexamethasone. Dexamethasone improved RyR–LTCC coupling and synchrony of intracellular Ca2+ release, but did not alter expression levels of t-system-associated proteins junctophilin-2 (JPH2), bridging integrator-1 (BIN1) or caveolin-3 (CAV3). Rather, dexamethasone upregulated LC3B and increased autophagic flux. The broad-spectrum protein kinase inhibitor staurosporine prevented dexamethasone-induced upregulation of autophagy and t-system preservation, and autophagy inhibitors bafilomycin A and chloroquine accelerated t-system loss. Conversely, induction of autophagy by rapamycin or amino acid starvation preserved the t-system. These findings suggest that GR signalling and autophagy are critically involved in t-system preservation and remodelling in the heart.
CRIS-Team Scopus Importer:2019-11-08
Keywords: Autophagy; Calcium signalling; Excitation–contraction coupling; Glucocorticoid receptor; Heart failure; Remodelling; Transverse tubular system

Healthcare status of adults with pulmonary hypertension due to congenital heart disease - Busse, Amely J.; Freilinger, Sebastian; Eicken, Andreas; Ewert, Peter; Freiberger, Annika; Huntgeburth, Michael; Nagdyman, Nicole; Von Scheidt, Fabian; Kaemmerer, Harald; Weyand, Michael (Cardiovascular Diagnosis and Therapy, 2022)
Background: In the long-term course of treated and untreated congenital heart defects (CHD), pulmonary hypertension (PH) is one of the most relevant complications. Since PH carries a high risk for mortality and morbidity, it is important to improve the status of healthcare and medical knowledge regarding the affected patients. Therefore, this study aimed to determine the current medical care status, health-related knowledge, and specific counseling needs of adults with various forms of CHD (ACHD) who are at increased risk of developing PH, as well as those with manifest PH. Methods: In this retrospective cross-sectional study, a representative sample of 803 ACHD were analyzed. Patients were split into three groups based on CHD: low risk for PH, at risk for pre- or post-capillary PH, and manifest PH. Data collection took place between September 2017 until February 2018 in a tertiary care center for ACHD. Healthcare status and specific needs for information or advice were analyzed using a questionnaire designed by our group. The state of knowledge of the patients was assessed by comparing this questionnaire and the corresponding medical records. Results: Both patients with manifest PH (n=51) and patients at risk to develop PH (n=629) were insufficiently informed about their health status, specific care structures available to them, and patient organizations. About 50% of the patients had specific counseling needs, especially regarding physical capability and sports, daily stress, rehabilitation measures, and pregnancy. Only 47.8% of patients with manifest PH were aware of suffering from PH (P<0.001). In particular, the patients had large knowledge deficits regarding comorbidities related to their health condition. Conclusions: PH is a quantitatively and qualitatively underestimated residuum or sequela of CHD that significantly affects outcome and prognosis in ACHD. Multidisciplinary, structured, and specific counseling of affected individuals with corresponding risk constellations is urgently needed. A prerequisite for this is closer collaboration between primary care physicians (PCPs), such as general practitioners, family physicians, internists, or general cardiologists, and ACHD specialists. Targeted patient counseling and care could have a positive impact on the level of awareness of those affected and favorably influence their prognosis.
CRIS-Team WoS Importer:2022-12-16

Huge coronary artery fistula to the pulmonary artery - Strecker, Thomas; Nooh, Ehab; Weyand, Michael; Agaimy, Abbas (Journal of Cardiac Surgery, 2019)
CRIS-Team Scopus Importer:2019-05-07

Human Cytomegalovirus infection leads to elevated levels of transplant arteriosclerosis in a humanised mouse aortic xenograft model - Heim, Christian; Weyand, Michael; Stamminger, Thomas; Ensminger, Stephan; et al. (American Journal of Transplantation, 2012)

Impact of medical treatment on long-term results after surgical ablation of atrial fibrillation in cardiac surgical patients - Feyrer, Richard; Ballazhi, Fatos; Seitz, Timo; Weyand, Michael; Harig, Frank (Annals of Thoracic and Cardiovascular Surgery, 2014)
The aim of this study was to evaluate the long-term outcome (4 years) of high-intensity-focused-ultrasound (HIFU) cardiac ablation, the significance of postablation antiarrhythmic drugs (AADs) and predictors of successful sinus rhythm (SR) restoration.103 patients were prospectively enrolled in a single-center study. The preoperative atrial fibrillation (AF) type was paroxysmal in 36%, permanent in 53%, persistent in 5% and flutter in 6% patients. The left atrial diameter was <50 mm in 78 patients and >50 mm in 25. Long-term results, up to 4 years, and postablation antiarrhythmics were evaluated. Follow-up studies including 12-lead electrocardiogram (ECG) and 24-h Holter ECG obtained at 3 and 6 months in our institute, and 12, 24, and 48 months during outpatient visits.No device- or procedure-related complications or deaths were observed. A pacemaker was implanted in 5% patients. Freedom from AF and flutter at 6-/12-/and 48-month visit were 66%/63%/68% for the entire population, 84%/77%/90% in patients with paroxysmal AF, 50%/46%/40% in patients with permanent AF and at any time in all 6 patients with flutter. No significant changes were noted at 2 years.Postablation results were not statistically different in patients on or not on antiarrhythmic therapy. At discharge, 53% of patients on antiarrhythmics and 55%, not on AADs were free of AF. At the 6-month visit, 66% of patients on AADs versus 69% of patients, not on AADs presented with SR, an improved outcome by 13 percentage points with AADs versus 14 percentage points without AADs (p = 0.65). Patients taking a ?-blocker showed better results in restoration/maintenance of SR after 6 months. No significant difference was noted regarding the use of UltraWand.Sixty-seven percent with a left atrium (LA) diameter <50 mm were successfully converted into SR, vs. 48% with an LA diameter >50 mm. Best results were achieved in patients with paroxysmal AF and LA <50 mm with 81% freedom of AF.AF treatment with HIFU ablation during concomitant cardiac surgery is a safe and effective procedure for restoring SR, especially in patients with AF and especially in patients with a smaller left atrial diameter. No significant difference was noted between the antiarrhythmic and non drug groups regarding restoration and maintaining SR; however, better results were achieved by those taking a ?-blocker.
EVALuna2:16084

Improving medical care and prevention in adults with congenital heart disease-reflections on a global problem-part I: development of congenital cardiology, epidemiology, clinical aspects, heart failure, cardiac arrhythmia - Neidenbach, Rhoia; Niwa, Koichiro; Oto, Oeztekin; Oechslin, Erwin; Aboulhosn, Jamil; Celermajer, David; Schelling, Joerg; Pieper, Lars; Sanftenberg, Linda; Oberhoffer, Renate; De Haan, Fokko; Weyand, Michael; et al. (Cardiovascular Diagnosis and Therapy, 2018)
Today most patients with congenital heart defects (CHD) survive into adulthood. Unfortunately, despite relevant residua and sequels, follow-up care of adults with congenital heart disease (ACHD) is not performed in specialized and/or certified physicians or centres. Major problems in the long-term course encompass heart failure, cardiac arrhythmias, heart valve disorders, pulmonary vascular disease, infective endocarditis, aortopathy and non-cardiac comorbidities. Many of them manifest themselves differently from acquired heart disease and therapy regimens from general cardiology cannot be transferred directly to CHD. It should be noted that even simple, postoperative heart defects that were until recently considered to be harmless can lead to problems with age, a fact that had not been expected so far. The treatment of ACHD has many special features and requires special expertise. Thereby, it is important that treatment regimens from acquired heart disease are not necessarily transmitted to CHD. While primary care physicians have the important and responsible task to set the course for adequate diagnosis and treatment early and to refer patients to appropriate care in specialized ACHD-facilities, they should actively encourage ACHD to pursue follow-up care in specialized facilities who can provide responsible and advanced advice. This medical update emphasizes the current data on epidemiology, heart failure and cardiac arrhythmia in ACHD.
EVALuna2:35958

Improving medical care and prevention in adults with congenital heart disease-reflections on a global problem-part II: infective endocarditis, pulmonary hypertension, pulmonary arterial hypertension and aortopathy - Neidenbach, Rhoia; Niwa, Koichiro; Oto, Oeztekin; Oechslin, Erwin; Aboulhosn, Jamil; Celermajer, David; Schelling, Joerg; Pieper, Lars; Sanftenberg, Linda; Oberhoffer, Renate; De Haan, Fokko; Weyand, Michael; et al. (Cardiovascular Diagnosis and Therapy, 2018)
Despite relevant residua and sequels, follow-up care of adults with congenital heart disease (ACHD) is too often not performed by/in specialized and/or certified physicians or centers although major problems in the long-term course may develop. The most relevant encompass heart failure, cardiac arrhythmias, heart valve disorders, pulmonary vascular disease, infective endocarditis (IE), aortopathy and non-cardiac comorbidities. The present publication emphasizes current data on IE, pulmonary and pulmonary arterial hypertension and aortopathy in ACHD and underlines the deep need of an experienced follow-up care by specialized and/or certified physicians or centers, as treatment regimens from acquired heart disease can not be necessarily transmitted to CHD. Moreover, the need of primary and secondary medical prevention becomes increasingly important in order to reduce the burden of disease as well as the socioeconomic burden and costs in this particular patient group.
EVALuna2:35959

Incidental finding of a giant asymptomatic right atrial tumor - Strecker, Thomas; Agaimy, Abbas; Zelzer, Peter; Weyand, Michael; Wachter, David Lukas (International Journal of Clinical and Experimental Pathology, 2014)
Primary cardiac tumors are very rare, atrial myxoma being the most common benign tumor of the heart. They may present with a great variety of incidental asymptomatic masses to severe life-threatening cardiovascular complications necessitating emergency surgery. Here we report the diagnostic evaluation and successful surgical resection of such a giant cardiac tumor which was found on a routine medical check-up in a 62-year-old patient. Histology confirmed diagnosis of unusually huge myxoma. This article demonstrates it's necessary to include cardiac tumors in the differential diagnosis of subtle and non-specific cardiothoracic symptoms.
EVALuna2:6611

Incidental papillary fibroelastoma of the tricuspid valve - Strecker, Thomas; Scheuermann, Sabine; Nooh, Ehab; Weyand, Michael; Agaimy, Abbas (Journal of Cardiothoracic Surgery, 2014)
Primary cardiac tumors are very rare, papillary fibroelastoma (PFE) being the second most common benign tumor of the heart in previous series. However, as a consequence of increased imaging examinations, incidental PFE may represent the most common cardiac tumor. Their clinical presentation varies from incidental asymptomatic masses to severe life-threatening cardiovascular complications necessitating emergency surgery. Here we report the diagnostic evaluation and successful surgical resection of such a cardiac tumor in a 67-year-old woman. Histology confirmed diagnosis of a papillary fibroelastoma. This report demonstrates it's necessary to include cardiac tumors in the differential diagnosis of subtle and non-specific cardiothoracic symptoms.
EVALuna2:6684

Inductive transcutaneous energy transfer for cardiac assist devices – pushing the limits - Kirchner, Jens; Ebel, Nina; Kinner, Sarah; Fischer, Georg; Werner, Siegfried; Schubert, Dirk W.; Weyand, Michael (22. Chirurgische Forschungstage, 2018)
Background / Purpose Power supply is an essential component of active implants. To provide energy across the skin barrier, inductive energy transfer is well established in low-power devices like Cochlea implants. However, current designs are not applicable to high-power implants like cardiac assist devices due to strong tissue heating, caused by local spots of high magnetic field strength associated with large heat dissipation. Here, we propose a system design that overcomes this problem. Methods To avoid the “hot spots”, the magnetic field is guided and thus homogenized by composite coil cores based on liquid silicon rubber (LSM), which permits to design appropriate gradients of permeability. Furthermore, the frequency is kept below 1 MHz to reduce dielectric losses within the body. LSM is a biocompatible material, whose flexibility allows adaption to the body surface to minimize the gap between extracorporeal and implanted coil. For analysis and optimization of coil and coil core design, the FEM software COMSOL Multiphysics® 5.3 was used. Results The simulations showed that with the proposed coil and coil core design the magnetic fields can be homogenized such that 24 W can be transferred with an efficiency of 98.8% and a temperature increase in the tissue of only 0.8°C. Conclusions These findings suggest the possibility to make inductive energy transfer applicable also for high‑power active implants such as ventricular assist devices, reducing the number of complications of VAD-patients.
Keywords: Inductive energy transfer; transcutaneous energy transfer; cardiac assist device

INFLUENCE OF B-CATENIN ON THE PROLIFERATION OF VASCULAR SMOOTH MUSCLE CELLS AND THE DEVELOPMENT OF CARDIAC ALLOGRAFT VASCULOPATHY IN MICE - Heim, Christian; Kuckhahn, Annika; Ramsperger-Gleixner, Martina; Distler, Jörg; Spriewald, Bernd M.; Weyand, Michael; Ensminger, Stephan M. (TRANSPLANTATION, 2020)
CRIS-Team WoS Importer:2021-03-05

INFLUENCE OF SEROTONIN (5-HT) RECEPTOR TYPE 2 ANTAGONISTS ON THE DEVELOPMENT OF TRANSPLANT VASCULOPATHY IN A MODEL OF MURINE AORTIC TRANSPLANTATION - Gocht, A.; Distler, Jörg; Ensminger, S.; Spriewald, B.; Ramsperger-Gleixner, Martina; Weyand, Michael; Heim, Christian (2016)
EVALuna2:35054

Inhibition of TNF-alpha reduces transplant arteriosclerosis in a murine aortic transplant model. - Wollin, Martina; Abele, Silke; Bruns, Heiko; Weyand, Michael; Kalden, Joachim; Ensminger, Stephan M.; Spriewald, Bernd M. (Transplant International, 2009)
Experimental and clinical data provide evidence that TNF-alpha contributes to acute and chronic allograft rejection. In this study, we explored the effect of TNF-alpha blockade using the chimeric monoclonal antibody infliximab on the development of transplant arterisoclerosis in a fully mismatched aortic allograft model. Post-transplant treatment of CBA (H2(k)) recipients with 250 mug infliximab (cumulative dose 1.25 mg) reduced luminal occlusion of C57Bl/6 (H2(b)) aortic grafts on day 30 from 77 +/- 5% in untreated controls to 52 +/- 6%. Increasing the dose of anti-TNF-alpha antibody had no further beneficial effect. Treatment with human control immunoglobulin had no effect on intima proliferation. Under TNF-alpha blockade, ICAM-1 and PDGF mRNA expression within the grafts was strongly reduced, whereas iNOS expression was enhanced. The data show that TNF-alpha blockade using infliximab can reduce the development of transplant arteriosclerosis in fully mismatched murine aortic grafts.

Interleukin-3 protects against viral pneumonia in sepsis by enhancing plasmacytoid dendritic cell recruitment into the lungs and T cell priming - Benard, Alan; Hansen, Frederik; Uhle, Florian; Klösch, Bettina; Czubayko, Franziska; Mittelstädt, Anke; Jacobsen, Anne; David, Paul; Podolska, Malgorzata; Anthuber, Anna; Swierzy, Izabela; Schaack, Dominik; et al. (Frontiers in Immunology, 2023)
Rationale: Sepsis, a global health burden, is often complicated by viral infections leading to increased long-term morbidity and mortality. Interleukin-3 (IL-3) has been identified as an important mediator amplifying acute inflammation in sepsis; however, its function in the host response to viral infections during sepsis remains elusive. Objectives: To investigate the role of IL-3 during viral pneumonia in sepsis. Methods: We included septic patients from two different cohorts and used in vitro and in vivo assays. The obtained data were substantiated using a second model (SARS-CoV-2 infections). Measurements and main results: Low plasma IL-3 levels were associated with increased herpes simplex virus (HSV) airway infections in septic patients, resulting in reduced overall survival. Likewise, Il-3-deficient septic mice were more susceptible to pulmonary HSV-1 infection and exhibited higher pulmonary inflammation than control mice. Mechanistically, IL-3 increases innate antiviral immunity by promoting the recruitment of circulating plasmacytoid dendritic cells (pDCs) into the airways and by enhancing pDC-mediated T cell activation upon viral stimulation. Interestingly, the ability of IL-3 to improve adaptive immunity was confirmed in patients with SARS-CoV-2 infections. Conclusion: Our study identifies IL-3 as a predictive disease marker for viral reactivation in sepsis and reveals that IL-3 improves antiviral immunity by enhancing the recruitment and the function of pDCs.
CRIS-Team Scopus Importer:2023-03-24
Keywords: interleukin-3; plasmacytoid dendritic cells; sepsis; T cell priming; viral pneumonia

Intraoperative visualization of a deformed left main stent during surgical aortic valve replacement - Müller, Philipp; Heim, Christian; Weyand, Michael; Harig, Frank (Journal of Cardiothoracic Surgery, 2023)
Background: While coronary artery bypass grafting is typically considered first choice for the treatment of left main stenosis, there is a trend towards left main stenting due to a steadily aging population in western countries with a high operative risk and patients with single vessel coronary artery disease affecting the left main artery. Nevertheless left main stenting remains controversial, especially in patients with concomitant indications for open-heart surgery. Case presentation: We want to present a case of a 78-year-old male patient with high-grade aortic stenosis who underwent surgical aortic valve replacement at our heart center due to anatomical contraindications for transcatheter aortic valve replacement. Stenting of the left main coronary artery was performed three years earlier due to single vessel coronary artery disease while moderate aortic valve stenosis was under surveillance at the time of the intervention. Intraoperatively we found the stent to be deformed inside the left main coronary artery, covering nearly 25% of the coronary ostium. So injection of cardioplegia directly into this ostium, as we perform normally, was not possible without further damaging the stent and/or the opening of the ostium. We had to insert cardioplegia via the retrograde way, so via the coronary sinus. Conclusion: While left main stenting can be reasonable for a specific population of patients, it should be used cautiously in patients with concomitant indications for open-heart surgery in the near future and a low perioperative risk profile.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Aortic valve replacement; Cardiac surgery; Cardiology; Coronary artery disease; Left main stenosis; Left main stenting; Stenting

Late-Onset Aspergillus Fumigatus Infection of an Aortic Stent Graft in an Immunocompetent Patient - Ballazhi, Fatos; Weyand, Michael; Lang, Werner; Schoerner, Christoph; Seitz, Tatjana (Thoracic and Cardiovascular Surgeon Reports, 2015)
Aspergillus fumigatus as a clinical entity is difficult to diagnose. We present a case, which could facilitate diagnosis and management of the aforementioned disease. A 60-year-old man with stent graft implantation in the descending aorta (6 years ago) presented with fever, night sweats, and weight loss over 5 months. Leukocytosis and elevated C-reactive protein were constantly spiking. Blood cultures were negative. Notably, the serum immunoglobulin E (IgE) level was strongly elevated (> 1,000 U/mL). Anamnestically, the patient suffered from a mild form of atopic dermatitis and bronchial asthma. The pulmonary status showed no abnormalities in the computed tomography image. Nonetheless, a chest scan revealed a suspected abscess around the stent graft of the descending aorta. Extra-anatomic ascending to descending aortic bypass (Gelsoft 22 mm, Vascutek, Juchinnan, Scotland, United Kingdom) was performed. Intraoperative samples revealed A. fumigatus. These findings were confirmed by polymerase chain reaction analysis. Infection by A. fumigatus represents a diagnostic challenge because blood cultures are usually negative, but expeditious treatment is required to prevent occurrence of irreversible complications. A late graft infection, possibly caused by A. fumigatus should be suspected in patients with implanted grafts, who suffer from unexplained, blood culture-negative fever that does not respond to antibiotics and who have a history of dermatitis or bronchial asthma with elevated IgE antibodies.
EVALuna2:7685

Left Atrial Appendage Occlusion on a Beating Heart during Minimally Invasive Valve Surgery Using an Aortic Endoclamp: A Case Report - Suleiman, Mathieu; Kaemmerer, Ann-Sophie; Fechner, Jörg; Nooh, Ehab; Weyand, Michael; Heim, Christian (Journal of Clinical Medicine, 2023)
Concomitant LAA occlusion has been shown to be an effective and safe treatment for patients with atrial fibrillation during cardiac surgery to prevent embolic stroke. Minimally invasive procedures are challenging due to restricted access to and visibility of the surgical site. Also, aortic endoclamping has been developed as an alternative surgical approach to exoclamping. The aim of this article is to demonstrate the method of beating heart LAA occlusion with the Atriclip® (AtriCure, Mason, OH, USA) device during minimally invasive mitral valve surgery while using the endoclamping alternative for aortic cross-clamping.
CRIS-Team Scopus Importer:2023-10-20
Keywords: AtriClip; IntraClude Device; minimally invasive surgery; mitral valve prolapse; mitral valve replacement

LEFT VENTRICULAR ASSIST DEVICE EXPLANTATION AFTER CARDIAC RECOVERY - Heim, Christian; Aziz, Saya; Weyand, Michael; Tandler, Rene (TRANSPLANTATION, 2020)
CRIS-Team WoS Importer:2021-03-05

Lipomatous Hypertrophy of the Atrial Septum in a Patient Undergoing Coronary Artery Bypass Surgery - Strecker, Thomas; Weyand, Michael; Agaimy, Abbas (Case Reports in Pathology, 2016)
Background. Lipomatous hypertrophy of the atrial septum (LHAS) is a rare entity characterized by mass-forming deposition of fatty tissue within the atrial septum. To date, <300 cases have been reported; many of them were autopsy findings. The clinical presentation of LHAS varies from incidental asymptomatic mass (most frequent form) to severe life-threatening cardiovascular complications necessitating emergency cardiac surgery. Case Presentation. Here, we present the successful surgical resection of such a massive LHAS which was found incidentally on preoperative investigation of a 71-year-old patient with progressive coronary heart disease. Histology confirmed the diagnosis of lipomatous hypertrophy of the atrial septum. Conclusions. The described case report illustrates an unusual example of LHAS in a patient undergoing a planned coronary artery bypass surgery. In this case, surgical intervention was justified to avoid later outflow obstructions.
EVALuna2:6927

Long-Term Cultivation of Human Atrial Myocardium - Klumm, Maximilian J.; Heim, Christian; Fiegle, Dominik; Weyand, Michael; Volk, Tilmann; Seidel, Thomas (Frontiers in Physiology, 2022)
Organotypic culture of human ventricular myocardium is emerging in basic and translational cardiac research. However, few institutions have access to human ventricular tissue, whereas atrial tissue is more commonly available and important for studying atrial physiology. This study presents a method for long-term cultivation of beating human atrial myocardium. After written informed consent, tissues from the right-atrial appendage were obtained from patients with sinus rhythm undergoing open heart surgery with cardiopulmonary bypass. Trabeculae (pectinate muscles) prepared from the samples were installed into cultivation chambers at 37°C with a diastolic preload of 500 μN. After 2 days with 0.5 Hz pacing, stimulation frequency was set to 1 Hz. Contractile force was monitored continuously. Beta-adrenergic response, refractory period (RP) and maximum captured frequency (fmax) were assessed periodically. After cultivation, viability and electromechanical function were investigated, as well as the expression of several genes important for intracellular Ca2+ cycling and electrophysiology. Tissue microstructure was analyzed by confocal microscopy. We cultivated 19 constantly beating trabeculae from 8 patient samples for 12 days and 4 trabeculae from 3 specimen for 21 days. Functional parameters were compared directly after installation (0 d) with those after 12 d in culture. Contraction force was 384 ± 69 μN at 0 d and 255 ± 90 μN at 12 d (p = 0.8, n = 22), RP 480 ± 97 ms and 408 ± 78 ms (p = 0.3, n = 9), fmax 3.0 ± 0.5 Hz and 3.8 ± 0.5 Hz (p = 0.18, n = 9), respectively. Application of 100 nM isoprenaline to 11 trabeculae at 7 d increased contraction force from 168 ± 35 μN to 361 ± 60 μN (p < 0.01), fmax from 6.4 ± 0.6 Hz to 8.5 ± 0.4 Hz (p < 0.01) and lowered RP from 319 ± 22 ms to 223 ± 15 ms. CACNA1c (L-type Ca2+ channel subunit) and GJA1 (connexin-43) mRNA expressions were not significantly altered at 12 d vs 0 d, while ATP2A (SERCA) and KCNJ4 (Kir2.3) were downregulated, and KCNJ2 (Kir2.1) was upregulated. Simultaneous Ca2+ imaging and force recording showed preserved excitation-contraction coupling in cultivated trabeculae. Confocal microscopy indicated preserved cardiomyocyte structure, unaltered amounts of extracellular matrix and gap junctions. MTT assays confirmed viability at 12 d. We established a workflow that allows for stable cultivation and functional analysis of beating human atrial myocardium for up to 3 weeks. This method may lead to novel insights into the physiology and pathophysiology of human atrial myocardium.
CRIS-Team Scopus Importer:2022-03-25
Keywords: calcium imaging; confocal microscopy; gene expression; human atrium; in vitro; refractory period; tissue culture

Medical care of adults with congenital heart diseases : Present and future - Neidenbach, R.; Achenbach, Stephan; Andonian, C.; Beckmann, J.; Biber, S.; Dittrich, Sven; Ewert, P.; Freilinger, S.; Huntgeburth, M.; Nagdyman, N.; Oberhoffer, R.; Pieper, L.; et al. (Herz, 2019)
Congenital heart diseases (CHD) are the most common types of congenital organ defects. Thanks to medical progress in congenital cardiology and heart surgery, most children with CHD reach adulthood. Despite primarily successful treatment residual and subsequent conditions as well as (non)cardiac comorbidities can influence the chronic course of the disease and lead to a higher morbidity and mortality. Adults with congenital heart disease (ACHD) in Germany are not tied to the healthcare structure despite the great need for aftercare. According to the results of the medical care of ACHD (MC-ACHD) study, ACHD centers and specialists in Germany are insufficiently perceived despite increased complication rates and the great need for specialist guidance. General practitioners and patients are not adequately informed about existing ACHD facilities. A better awareness of the ACHD problem should be created at the level of primary medical supply in order to optimize care and to reduce morbidity and mortality. Improved future-oriented patient care includes lifelong regular follow-up and the possibility of interdisciplinary, integrated medical care of CHD.
EVALuna2:212989

Medizinische Versorgung von Erwachsenen mit angeborenen Herzfehlern: Gegenwart und Zukunft - Neidenbach, R.; Achenbach, Stephan; Andonian, C.; Beckmann, J.; Biber, S.; Dittrich, Sven; Ewert, P.; Freilinger, S.; Huntgeburth, M.; Nagdyman, N.; Oberhoffer, R.; Pieper, L.; et al. (Herz, 2019)
Congenital heart diseases (CHD) are the most common types of congenital organ defects. Thanks to medical progress in congenital cardiology and heart surgery, most children with CHD reach adulthood. Despite primarily successful treatment residual and subsequent conditions as well as (non)cardiac comorbidities can influence the chronic course of the disease and lead to a higher morbidity and mortality. Adults with congenital heart disease (ACHD) in Germany are not tied to the healthcare structure despite the great need for aftercare. According to the results of the medical care of ACHD (MC-ACHD) study, ACHD centers and specialists in Germany are insufficiently perceived despite increased complication rates and the great need for specialist guidance. General practitioners and patients are not adequately informed about existing ACHD facilities. A better awareness of the ACHD problem should be created at the level of primary medical supply in order to optimize care and to reduce morbidity and mortality. Improved future-oriented patient care includes lifelong regular follow-up and the possibility of interdisciplinary, integrated medical care of CHD.
CRIS-Team Scopus Importer:2019-08-06
Keywords: ACHD; Cardiology; Comorbidities; Congenital heart defects; Prevention

MELD-score for risk stratification in cardiac surgery - Pathare, Presheet; Elbayomi, Mohamed; Weyand, Michael; Griesbach, Colin; Harig, Frank (Heart and Vessels, 2023)
The outcome of the patients undergoing cardiac surgery with cardiopulmonary bypass (CPB) is also influenced by the renal and hepatic organ functions. Risk stratification, using scores such as EURO Score II or STS Short-Term Risk Calculator for patients undergoing cardiac surgery with cardiopulmonary bypass, ignores the quantitative renal and hepatic function; therefore, MELD-Score was applied in these cases. We retrospectively examined patient data using the MELD score as a predictor of mortality. To perform a univariate analysis of the data, patients were classified into three groups based on the MELD Score: MELD < 10 (Group 1), MELD 10 to 19 (Group 2), and MELD ≥ 20 (Group 3). A total of 11,477 participants were included in the study, though several patients with either missing MELD scores or lack of creatinine, bilirubin, or INR levels were dropped from the original cohort. Eventually, 10,882 patients were included in the analysis. The primary outcome was defined as postoperative, in-hospital mortality. Secondary outcomes such as postoperative bleeding, including the requirement for repeat thoracotomy, postoperative neurological complications, and assessment of catecholamines on weaning from cardiopulmonary bypass/ requirement of mechanical circulatory support were examined. A higher MELD score was associated with increased postoperative mortality. Patients with MELD > 20 experienced a 31.2% postoperative mortality, compared to Group 1 (4.6%) and Group 2 (17.5%). The highest rates of postoperative bleeding (13.8%) and, repeat thoracotomy (13.2%) & postoperative pneumonia (17.4%) were seen in Group 3 (threefold increase when compared to Group 1, renal failure requiring dialysis (N = 235, 2.7% in Group 1 v/s N = 78, 22.9% in Group 3) or requiring high dose catecholamines post-operatively or mechanical circulatory support (IABP/ECLS). Incidentally, an increased MELD Score was not associated with a significant increase in the postoperative incidence of stroke/TIA or the presence of sternal wound infections/complications. A higher mortality was observed in patients with reduced liver and renal function, with a significant increase in patients with a MELD score > 20. As the current risk stratification scores do not consider this, we recommend applying the MELD score before considering patients for cardiac surgery.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Cardiac surgery; Liver disease; MELD; Preoperative

Mesothelial/monocytic incidental cardiac excrescences (cardiac MICE) associated with acute aortic dissection: a study of two cases - Strecker, Thomas; Bertz, Simone; Wachter, David Lukas; Weyand, Michael; Agaimy, Abbas (International Journal of Clinical and Experimental Pathology, 2015)
Acute aortic dissection is a life-threatening condition mainly caused by hypertension, atherosclerotic disease and other degenerative diseases of the connective tissue of the aortic wall. Mesothelial/monocytic incidental cardiac excrescences (cardiac MICE) is a rare benign reactive tumor-like lesion composed of admixture of histiocytes, mesothelial cells, and inflammatory cells set within a fibrinous meshwork without a vascular network or supporting stroma. Cardiac MICE occurring in association with aortic dissection is exceptionally rare (only one such case reported to date). We herein report on the surgical repair of two Stanford type A aortic dissections caused by idiopathic giant cell aortitis in a 66-year-old-woman and by atherosclerotic disease in a 58-year-old-man, respectively. In both cases, the dissections could be visualized via computed tomography. Histopathology showed cardiac incidental MICE within the external aortic wall near the pericardial surface which was confirmed by immunohistochemistry.
EVALuna2:6704

Microvascular Integrity Can Be Preserved by Anti-Platelet Therapy and in Combination with mTOR Inhibitor - Heim, Christian; Khan, M. A.; Motsch, B.; Gocht, A.; Ramsperger-Gleixner, Martina; Stamminger, T.; Nicolls, M. R.; Weyand, Michael; Ensminger, S. M. (2017)
EVALuna2:33769

Microvascular integrity plays an important role for graft survival after experimental skin transplantation - Motsch, Benjamin; Heim, Christian; Koch, Nina; Ramsperger-Gleixner, Martina; Weyand, Michael; Ensminger, Stephan M. (Transplant Immunology, 2015)
Every transplanted organ relies on a reliable and sound vascular system. Therefore, our study focused on the investigation if platelet inhibition alone or combined with mTOR-inhibition has a beneficial effect on the microvascular integrity in allogeneic murine skin grafts.Skin transplantation was performed from fully MHC-mismatched C57BL/6 (H-2b) donors to CBA/J (H-2k) recipient mice. Skin allograft recipients were assigned to several experimental groups and either treated with clopidogrel alone, everolimus alone or a combination of both. Graft survival was evaluated and transplants were harvested after 8 days and analyzed for CD31 and C4d by immunohistochemistry.Untreated allografts showed a reduced amount of CD31 on postoperative day 8 as well as an increase in C4d compared to isografts. All treated animals showed a significant improvement regarding CD31 [1577.7 ± 200.4 (clopidogrel)/1702.8 ± 151.1 (clopidogrel + everolimus) vs. 479.7 ± 184.2 (control), n = 8, p b 0.05] and C4d [420.9 ± 70.9 (clopidogrel)/324.5 ± 77.3 (clopidogrel + everolimus) vs. 772.4 ± 159.7 (control), n = 8, p b 0.05]. In addition, skin grafts of animals treated with clopidogrel and everolimus survived significantly longer compared to untreated controls [19.2 ± 4.2 d vs. 12.8 ± 2.4 d, n= 10, p b 0.05].In this study we could show that clopidogrel alone and in combination with everolimus substantially improved microvascular integrity and resulted in increased survival time of skin grafts.
EVALuna2:16101

Microvasculature in murine tracheal allografts after combined therapy with clopidogrel and everolimus - Heim, Christian; Kuckhahn, Annika; Ramsperger-Gleixner, Martina; Nicolls, Mark R.; Weyand, Michael; Ensminger, Stephan M. (Interactive Cardiovascular and Thoracic Surgery, 2021)
OBJECTIVES: Survival after lung transplantation is mainly limited by the development of chronic lung allograft dysfunction. Previous studies have suggested T-cell mediated proliferation and microvascular changes in experimental small airways models as potential therapeutic targets. The aim of this study was to assess microvascular changes in murine orthotopic tracheal allografts after treatment with everolimus alone or in combination with clopidogrel. METHODS: C57Bl/6 (H-2b) donor tracheas were orthotopically transplanted into CBA (H-2k) recipients. Mice received daily injections of everolimus (0.05 mg/kg) alone or combined with clopidogrel (1 mg/kg). Twenty-eight days after transplantation, ratio of the thickness of tracheal epithelium and lamina propria was measured as an indicator for chronic rejection. Additionally, graft oxygenation and graft perfusion were detected on postoperative days 4, 10 and 28. Quantitative reverse transcription polymerase chain reaction analysis was used for gene expression analysis. RESULTS: While syngeneic grafts showed a stable tissue pO2 and undisturbed microvascular perfusion, rejecting allografts had a drastic decline in both parameters as well as a flattened epithelium and an increased thickness of the lamina propria. Treatment with everolimus reduced allogeneic fibroproliferation, but had no protective effects on the microvasculature; polymerase chain reaction analysis indicated hypoxic stress and inflammation. Combining everolimus with clopidogrel improved microvascular integrity in the tracheal grafts, but had no synergistic effect in preventing obliterative bronchiolitis development. CONCLUSIONS: These data demonstrate that the ability of everolimus to reduce the development of post-transplant obliterative bronchiolitis is not caused by microvascular protection and has no synergistic effects with clopidogrel in acute airway rejection.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Bronchiolitis obliterans syndrome; Chronic lung allograft dysfunction; Clopidogrel; Everolimus; Microvascular integrity; Obliterative bronchiolitis

Mitral Multifocal Papillary Fibroelastoma in a Patient with Aggressive Fibromatosis - Müller, Philipp; Agaimy, Abbas; Weyand, Michael; Heim, Christian (Thoracic and Cardiovascular Surgeon Reports, 2021)
Mitral valve fibroelastoma is a rare condition that can be associated with high morbidity rates due to thrombus formation and resulting embolic events. Causative treatment for affected patients is mitral valve surgery. An association between cardiac fibroelastoma and desmoid-type fibromatosis, an aggressive form of fibromatosis, is not yet described. We present a case of a 58-year-old man with a history of desmoid-type fibromatosis and concomitant papillary fibroelastoma of the mitral valve who consequently underwent mitral valve replacement.
CRIS-Team WoS Importer:2022-01-07

Murine cytomegalovirus infection leads to increased levels of transplant arteriosclerosis in a murine aortic allograft model - Heim, Christian; Abele-Ohl, Silke; Eckl, Sebastian; Ramsperger-Gleixner, Martina; Mahmoudian, Shohreh; Weyand, Michael; Stamminger, Thomas; Ensminger, Stephan M. (Transplantation, 2010)
Introduction. Cytomegalovirus infection after heart transplantation is considered as risk factor for the development of transplant arteriosclerosis. Therefore, the aim of this study was to investigate the effect of murine cytomegalovirus (MCMV) as a single risk factor on transplant arteriosclerosis in an experimental aortic allograft model. Methods. Major histocompatibility complex class I-mismatched aortas of C.B10-H2(b)/LilMcdJ donor were transplanted into BALB/c recipients, which were either mock-infected or infected with MCMV (strain Smith) on day 7 and harvested 37 days after transplantation. In one experimental group animals received a daily dose of everolimus to increase the viral load of recipients. Grafts were analyzed by histology, morphometry, and immunofluorescence. Intragraft cytokine mRNA production was analyzed by real-time polymerase chain reaction (PCR), and persistence of cytomegalovirus infection was confirmed by TaqMan PCR. Results. After infection with MCMV, there was significantly more intimal proliferation when compared with uninfected controls (intimal proliferation 83.5%±9.6% [MCMV+] vs. 43.9%±5.1% [MCMV+]), indicating that MCMV plays a role in the development of transplant arteriosclerosis. Even after treatment with everolimus, MCMV infection pronounced significantly more intimal proliferation (intimal proliferation 52.5%±7.3% [MCMV+] vs. 20.2%±1.7% [MCMV+]). Intragraft mRNA expression showed significantly higher production of CD62E, intercellular adhesion molecule-1, and vascular cell adhesion molecule-1 after infection with MCMV. Cellular infiltration revealed significantly more CD4+, CD8+, and dendritic cells. We could also confirm the presence of MCMV for the duration of the experimental protocol by PCR within the spleen, liver, salivary glands, lung, and the aortic transplant. Conclusion. These data suggest that MCMV infection plays an important role in the development of transplant arteriosclerosis. © 2010 by Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2024-06-04
Keywords: Adhesion molecules; Dendritic cells; Murine cytomegalovirus; Transplant arteriosclerosis

New Targets for the Prevention of Chronic Rejection after Thoracic Organ Transplantation - Heim, Christian; Gocht, Annika; Weyand, Michael; Ensminger, Stephan (Thoracic and Cardiovascular Surgeon, 2018)

Nintedanib reduces alloimmune-induced chronic airway changes in murine tracheal allografts - Mauer, Julia; Kuckhahn, Annika; Ramsperger-Gleixner, Martina; Ensminger, Stephan M.; Distler, Jörg; Weyand, Michael; Heim, Christian (Transplant Immunology, 2022)
Background: The major obstacle for long-term survival after successful lung transplantation is the development of bronchiolitis obliterans (BO) which is one phenotype of chronic lung allograft dysfunction (CLAD). Nintedanib has beneficial effects treating neoplastic diseases and idiopathic pulmonary fibrosis by blocking tyrosine kinase receptors. These receptors play an important role in alloimmune-mediated proliferative diseases. The aim of this study was to determine the effect of nintedanib on proliferative airway changes after orthotopic trachea transplantation in mice. Methods: C57BL/6 mice (H-2b) donor tracheas were orthotopically transplanted into CBA/J mice (H-2k). After transplantation, recipients were daily treated with nintedanib (60 mg/kg; p.o.). Histological and immunofluorescence analysis were performed after 30 days and intragraft gene expression measurements after 14 days of treatment, respectively. Results: Tracheal allografts from mice treated with nintedanib showed significantly less features of chronic rejection than untreated allografts reflected in a higher epithelium/lamina propria ratio (ELR) [ELR: 0.65 ± 0.13 nintedanib vs. 0.50 ± 0.07 untreated controls; p < 0.05] and a reduced submucosal smooth muscle actin (SMA) content [SMA: 1.26% ± 0.78% nintedanib vs. 2.18% ± 1.01% untreated controls; p < 0.01]. Furthermore, lower T cell, macrophage and dendritic cell infiltration was detected in the nintedanib treated grafts. The protein and intragraft mRNA expression of receptor subtypes was considerably decreased in grafts of nintedanib treated mice. The mRNA expression of relevant immune mediators was affected by nintedanib treatment. Conclusion: Receptor blocking by nintedanib reduced alloimmune-induced inflammation and chronic airway changes in mouse trachea allografts and might be a promising approach to diminish the development of BO in lung transplants.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Bronchiolitis obliterans; Chronic rejection; Nintedanib; Tracheal allografts; Tyrosine kinase inhibitor

NR4A1 AGONIST CYTOSPORONE B DOES NOT ATTENUATE CAV IN A MOUSE MODEL DESPITE REPORTED ANTI-PROLIFERATIVE AND ANTI-INFLAMMATORY EFFECTS - Kuckhahn, A.; Ramsperger-Gleixner, Martina; Distler, Jörg; Weyand, Michael; Heim, Christian (TRANSPLANT INTERNATIONAL, 2020)
CRIS-Team WoS Importer:2020-11-06

Pass On What You Have Learned: A Structured Mentor-Mentee Concept for the Implementation of a Minimally Invasive Mitral Valve Surgery Program - Heim, Christian; Müller, Philipp; Massoudy, Parwis; Harig, Frank; Nooh, Ehab; Weyand, Michael; Czesla, Markus (European Surgical Research, 2021)
Introduction: Starting a minimally invasive cardiac surgery (MICS) for mitral valve repair (MVR) program is challenging as it requires a new learning curve, but compromising surgical results at the same time is not acceptable. Here, we describe our surgical educational experience of starting a new MICS program at a university heart center in Germany. Methods: A dedicated team for the new MICS program including 2 cardiac surgeons, 1 cardiac anesthetist, 1 perfusionist, and 1 scrub nurse was chosen. The use of long shafted instruments was trained in a low-cost self-assembled MICS simulator, and the EACTS endoscopic dry lab course was visited. Thereafter, 1 MICS center was visited for direct observation and peer-to-peer education for 6 weeks. The mentor observed the first 10 cases performed by the mentee. The surgical mitral valve expertise of 1 single cardiac surgeon was retrospectively analyzed between April 2016 and April 2021. Results: Before the implementation of the MICS-MVR program, 18 mitral valve operations have been performed through sternotomy between April 2016 and October 2018 including 12 replacements and 6 ring annuloplasties. After starting the MICS-MVR program, 73 mitral operations have been performed by the same surgeon of which 53 video-assisted through minithoracotomy (72.6%). 83.1% of the MICS procedures included complex repair (n = 38) and ring annuloplasty (n = 6). Open heart MV surgery was necessary in 20 patients due to concomitant procedures (n = 8), redo procedures (n = 2), severe endocarditis (n = 4), or contraindication for MICS such as PAD (n = 6). There have been no deaths, 1 stroke, and 1 cardiac vascular (RCX) complication. Two patients required conversion to sternotomy and one pericardiocentesis in the long term. Conclusion: Typically, excellent exposure and high repair rates of the MV has led us offer MICS approach to a majority of patients with isolated MV disease. Careful planning and a strict mentor-mentee concept facilitated a safe startup of an MICS program in a busy university heart center.
CRIS-Team WoS Importer:2021-12-17

Pathological findings in cardiac apex removed during implantation of left ventricular assist devices (LVAD) are non-specific: 13-year-experience at a German Heart Center - Strecker, Thomas; Roesch, Johannes; Weyand, Michael; Agaimy, Abbas (International Journal of Clinical and Experimental Pathology, 2014)
Ventricular assist devices (VAD) have become an established therapy for patients with end-stage heart failure. The two main reasons for this development are the shortage of appropriate donor organs and the increasing number of patients waiting for heart transplantation (HTX). Furthermore, the enormous advances in the technical equipment and the rising clinical experience have improved the implantation technique, the durability and the long-term patient outcomes.We reviewed all cases of left ventricular assist device (LVAD) implantation at our Erlangen Heart Center during January 2000-July 2013. The main aim of this study was to analyze the underlying pathology from the cardiac apex removed during the implantation. From all patients, we created a follow-up, analyzed the pathological features with the clinical diagnoses and described the overall outcome.VAD implantation was performed in 266 cases at our center in the last 13 years (2.2% of the total of 12254 cardiac surgical operations in that period). From these patients, 223 underwent LVAD or biventricular (BVAD) implantation; the remaining received a right (RVAD) implantation. The most frequent underlying clinical diagnoses were dilated (n = 84, 37.7%, DCM) or ischemic (n = 61, 27.4%, ICM) cardiomyopathy. The pathological findings in the apex biopsy were generally non-specific and showed variable interstitial myocardial fibrosis with evidence of fibre loss, fatty degeneration and variable irregular atrophy of muscle fibres, consistent with dilated and ischemic cardiomyopathies as the most frequent causes of heart failure in these patients. Only a few cases showed other specific features such as myocarditis and AL-amyloidosis.Pathological findings in cardiac apex removed during LVAD implantation are rather non-specific and they generally reflect the late stage or consequences of chronic myocardial damage in cases of dilated or ischemic cardiomyopathies. Variable patchy chronic inflammatory changes may be observed in cardiomyopathies as a non-specific reaction caused by myocardial fiber damage and should not lead to misinterpretation as evidence of myocarditis or revision of original diagnosis.
EVALuna2:6683

Patient-tailored silicone plug for HeartMate 3™ left ventricular assist device explantation - Elbayomi, Mohamed; Tandler, Rene; Ebel, Nina; Schubert, Dirk W.; Werner, Siegfried; Kondruweit, Markus; Weyand, Michael; Heim, Christian (Journal of Artificial Organs, 2023)
Patient-tailored silicone plug for HeartMate 3™ left ventricular assist device explantation in two successive males proceeded successfully. Given medical therapeutic advancements, FDA-approved plug systems designed by LVAD manufacturers themselves will be necessary for the near future to provide a safe and simple device explantation alternative that fulfills all regulatory standards.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Case report; HeartMate 3™; Ventricular assist device explantation

Patient-Tailored Silicone Plug for HeartMate 3 (TM) Left Ventricular Assist Device Explantation - Heim, Christian; Ebel, Nina; Schubert, Dirk W.; Werner, Siegfried; Kondruweit, Markus; Tandler, R.; Weyand, Michael (JOURNAL OF HEART AND LUNG TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2019-04-04

PDGF Receptor Blockade is Associated With Decreased Development of Cardiac Allograft Vasculopathy in a Murine Aortic Transplant Model - Heim, Christian; Gocht, A.; Distler, Jörg; Spriewald, B.; Ramsperger-Gleixner, Martina; Weyand, Michael; Ensminger, S. M. (2018)
EVALuna2:35008

Pericardectomy after pericarditis constrictiva led to onset of transplant kidney function after 98 days of anuric kidney graft: a case report - Wacker, Caroline; Weyand, Michael; Schiffer, Mario; Opgenoorth, Mirian (BMC Nephrology, 2020)
BACKGROUND: Constrictive pericarditis is easily overlooked and can lead to severe problems in hemodynamics and end-organ perfusion, in our patient leading to 98 days of anuria after living kidney transplantation. This was completely reversible after pericardectomy. CASE PRESENTATION: A 43-year-old female caucasian patient received a living kidney donation from her mother. She had developed end-stage renal disease 2 years prior due to nephrotic syndrome linked to graft-versus-host disease after allogenic stem-cell transplantation for aplastic anemia. The graft showed insufficient function already in the early postoperative phase. Dialysis was paused after surgery, but the patient developed hypervolemia with ascites and edema in the lower extremities. Doppler ultrasonography showed scarce perfusion, with intrarenal arterial waveforms without end-diastolic flow. The venous perfusion profiles showed pulsatile retrograde flow. There was no identifiable reason for a primary vascular perfusion problem on ultrasonography or transplant kidney angiography. Kidney transplant biopsy revealed no rejection but extensive acute tubular necrosis. Three weeks after transplantation, the patient developed an acute anuric graft failure caused by severe cardiac decompensation. Echocardiography revealed a previously unnoticed constrictive pericarditis, which could be confirmed in a cardio computed tomography scan. The constrictive pericarditis had not been apparent on previous x-rays, computed tomography scans, or echocardiographies, including those for transplantation evaluation. Conservative management of the constrictive pericarditis was not successful and the graft remained anuric. Eventually, the patient underwent pericardectomy 16 weeks after kidney transplantation. Shortly after surgery, the graft started urine production again, which significantly increased within a few days. The clearance improved and 2 weeks later, the patient was free from dialysis. CONCLUSIONS: This case illustrates that special attention should be given to the pericardium during transplant evaluation, especially for patients who previously underwent stem-cell transplantations, chemotherapy or radiation.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Case report; Constrictive pericarditis; Delayed graft function; Kidney transplant; Pericardectomy

Pericardial tamponade, a diagnostic chameleon: from the historical perspectives to contemporary management - Kaemmerer, Ann-Sophie; Alkhalaileh, Khaleel; Suleiman, Mathieu; Kopp, Markus; Hauer, Christine; May, Matthias; Uder, Michael; Weyand, Michael; Harig, Frank (Journal of Cardiothoracic Surgery, 2023)
Background: Pericardial tamponade (PT) early after cardiac surgery is a challenging clinical entity, not infrequently misrecognized and often only detected late in its course. Because the clinical signs of pericardial tamponade can be very unspecific, a high degree of initial suspicion is required to establish the diagnosis. In addition to clinical examination the deployment of imaging techniques is almost always mandatory in order to avoid delays in diagnosis and to initiate any necessary interventions, such as pericardiocentesis or direct cardiac surgical interventions. After a brief overview of how knowledge of PT has developed throughout history, we report on an atypical life-threatening cardiac tamponade after cardiac surgery. A 74-year-old woman was admitted for elective biological aortic valve replacement and aorto-coronary-bypass grafting (left internal mammary artery to left anterior descending artery, single vein graft to right coronary artery). On the 10th postoperative day, the patient unexpectedly deteriorated. She rapidly developed epigastric pain radiating to the left upper abdomen, and features of low peripheral perfusion and shock. There were no clear signs of pericardial tamponade either clinically or echocardiographically. Therefore, for further differential diagnosis, a contrast-enhanced computed tomography scan was performed under clinical suspicion of acute abdomen. Unexpectedly, active bleeding distally from the right coronary anastomosis was revealed. While the patient was prepared for operative revision, she needed cardiopulmonary resuscitation, which was successful. Intraoperatively, the source of bleeding was located and surgically relieved. The subsequent postoperative course was uneventful. Conclusions: In the first days after cardiac surgery, the occurrence of life-threatening situations, such as cardiac tamponade, must be expected. Especially if the symptoms are atypical, the entire diagnostic armamentarium must be applied to identify the origin of the complaints, which may be cardiac, but also non-cardiac. Central message: A high level of suspicion, immediate diagnostic confirmation, and rapid treatment are required to recognize and successfully treat such an emergency (Fig. 5). Perspective: Pericardial tamponade should always be considered as a complication of cardiac surgery, even when symptoms are atypical. The full range of diagnostic tools must be used to identify the origin of the complaints, which may be cardiac, but also non-cardiac (Fig. 5).
CRIS-Team Scopus Importer:2023-02-17
Keywords: Cardiac tamponade; Diagnostics; Historical aspects; Pericardial effusion; Postoperative complication

Poly(glycerol sebacate)(butylene succinate-dilinoleate) blends as candidate materials for cardiac tissue engineering - Boccaccini, Aldo R.; Aifantis, K.; Tallawi, Marwa; Rai, Ranjana; R-Gleixner, M.; Roerick, Olaf; Weyand, Michael; Roether, Judith; Schubert, Dirk W.; Kozlowska, A.; El Fray, Miroslawa; et al. (Macromolecular Symposia, 2013)
Poly (glycerol sebacate) (PGS) and poly (butylene succinate‐dilinoleate) (PBS‐DLA) are biodegradable polymers with potential application in cardiac tissue engineering. In the present study novel blends comprising PGS prepolymer and PBS‐DLA were prepared with varying compositions (70/30, 60/40, 50/50, 40/60, 30/70 and 0/100 in weight percentage). The physical, chemical, and mechanical properties of the PGS/PBS‐DLA blends were measured and compared. By adding PBS‐DLA to PGS the need for curing PGS prepolymer was eliminated, as the blended films are chemically stable. With increasing amount of PBS‐DLA the hydrophobicity of the blend system increased reaching values close to that of neat PBS‐DLA films. Furthermore, addition of PBS‐DLA significantly affected the mechanical properties of the blends, i.e. the elastic modulus of the blends was enhanced with increasing PBS‐DLA addition from 1.2 MPa to 54 MPa. At the same time, PBS‐DLA addition led to decreased degradation rate of the films. Furthermore the PBS‐DLA counteracted the acidity of the free carboxylic groups on the free end chains of the PGS prepolymer. In vitro cytocompatibility studies indicated high biocompatibility. Taken together the results confirm that the novel PGS/PBS‐DLA matrices exhibit promising characteristics as a biomaterial for application in cardiac regeneration approaches.
Keywords: myoblasts; poly (butylene succinate-dilinoleate); cardiac tissue engineering; mechanobiology; substrate stiffness

Poly(glycerol sebacate){Poly(butylene succinate-dilinoleate) Blends as Candidate Materials for Cardiac Tissue Engineering - Tallawi, Marwa; Rai, Ranjana; Ramsperger-Gleixner, Martina; Roerick, Olaf; Weyand, Michael; Roether, Judith; Schubert, Dirk W.; Kozlowska, A.; El Fray, Miroslawa; Aifantis, K.; Boccaccini, Aldo R.; et al. (WILEY-V C H VERLAG GMBH, 2013)
Poly (glycerol sebacate) (PGS) and poly (butylene succinate-dilinoleate) (PBS-DLA) are biodegradable polymers with potential application in cardiac tissue engineering. In the present study novel blends comprising PGS prepolymer and PBS-DLA were prepared with varying compositions (70/30, 60/40, 50/50, 40/60, 30/70 and 0/100 in weight percentage). The physical, chemical, and mechanical properties of the PGS/PBS-DLA blends were measured and compared. By adding PBS-DLA to PGS the need for curing PGS prepolymer was eliminated, as the blended films are chemically stable. With increasing amount of PBS-DLA the hydrophobicity of the blend system increased reaching values close to that of neat PBS-DLA films. Furthermore, addition of PBS-DLA significantly affected the mechanical properties of the blends, i.e. the elastic modulus of the blends was enhanced with increasing PBS-DLA addition from 1.2 MPa to 54 MPa. At the same time, PBS-DLA addition led to decreased degradation rate of the films. Furthermore the PBS-DLA counteracted the acidity of the free carboxylic groups on the free end chains of the PGS prepolymer. In vitro cytocompatibility studies indicated high biocompatibility. Taken together the results confirm that the novel PGS/PBS-DLA matrices exhibit promising characteristics as a biomaterial for application in cardiac regeneration approaches.
Keywords: cardiac tissue engineering; mechanobiology; myoblasts; poly (butylene succinate-dilinoleate); substrate stiffness

Poly(glycerol sebacate){Poly(butylene succinate-dilinoleate) Blends as Candidate Materials for Cardiac Tissue Engineering - Tallawi, Marwa; Rai, Ranjana; Ramsperger-Gleixner, Martina; Roerick, Olaf; Weyand, Michael; Roether, Judith; Schubert, Dirk W.; Kozlowska, A.; El Fray, M.; Aifantis, K.; Boccaccini, Aldo R.; et al. (Macromolecular Symposia, 2013)
Poly (glycerol sebacate) (PGS) and poly (butylene succinate-dilinoleate) (PBS-DLA) are biodegradable polymers with potential application in cardiac tissue engineering. In the present study novel blends comprising PGS prepolymer and PBS-DLA were prepared with varying compositions (70/30, 60/40, 50/50, 40/60, 30/70 and 0/100 in weight percentage). The physical, chemical, and mechanical properties of the PGS/PBS-DLA blends were measured and compared. By adding PBS-DLA to PGS the need for curing PGS prepolymer was eliminated, as the blended films are chemically stable. With increasing amount of PBS-DLA the hydrophobicity of the blend system increased reaching values close to that of neat PBS-DLA films. Furthermore, addition of PBS-DLA significantly affected the mechanical properties of the blends, i.e. the elastic modulus of the blends was enhanced with increasing PBS-DLA addition from 1.2 MPa to 54 MPa. At the same time, PBS-DLA addition led to decreased degradation rate of the films. Furthermore the PBS-DLA counteracted the acidity of the free carboxylic groups on the free end chains of the PGS prepolymer. In vitro cytocompatibility studies indicated high biocompatibility. Taken together the results confirm that the novel PGS/PBS-DLA matrices exhibit promising characteristics as a biomaterial for application in cardiac regeneration approache
Keywords: cardiac tissue engineering; mechanobiology; myoblasts; poly (butylene succinate-dilinoleate); substrate stiffness

Predictors and severity of intestinal ischaemia following on-pump cardiac surgery: a retrospective, propensity-matched analysis - Wiesmueller, Felix; Bryan, Darren S.; Krautz, Christian; Grützmann, Robert; Weyand, Michael; Strecker, Thomas (European Journal of Cardio-Thoracic Surgery, 2022)
OBJECTIVES: Risk factors associated with intestinal ischaemia after heart surgery have been previously explored; however, a paucity of data exists with regard to extent of intestinal ischaemia in patients requiring surgical intervention. The purpose of this study is to assess predictors of abdominal exploration and extent of ischaemia following cardiac surgery.
CRIS-Team WoS Importer:2022-03-11

Preservation of Microvascular Integrity in Murine Orthotopic Tracheal Allografts by Clopidogrel - Heim, Christian; Khan, Mohammad Afzal; von Silva-Tarouca, Benjamin; Kuckhahn, Annika; Stamminger, Thomas; Ramsperger-Gleixner, Martina; Nicolls, Mark R.; Weyand, Michael; Ensminger, Stephan M. (Transplantation, 2019)
BACKGROUND: Survival after lung transplantation is mainly limited by the development of chronic lung allograft dysfunction (CLAD). The aim of this study was to investigate if platelet inhibition by clopidogrel has a functionally relevant influence on the microvascular integrity of orthotopic tracheal allografts as an anatomic basis for the development of CLAD. METHODS: We orthotopically transplanted C57Bl/6 (H-2) tracheas into CBA.J (H-2) recipients who afterwards received clopidogrel (1 mg/kg). Morphometric analysis was performed by measuring epithelial height in proportion to thickness of the lamina propria (epithelium-lamina propria ratio). Tissue oxygenation was determined using a fluorescence quenching technique, and graft perfusion monitoring was performed by laser Doppler flowmetry and lectin-binding assay. Immunohistochemistry was used for detection of CD31 and inducible nitric oxide synthase while iron deposition was shown with Prussian blue reaction. Quantitative reverse transcription polymerase chain reaction analysis was used for gene expression analysis. RESULTS: Isografts maintained good oxygenation and perfusion throughout the experiment, while both were drastically reduced in allografts. Treatment with clopidogrel attenuated graft hypoxia and reduced loss of perfusion. Additionally, clopidogrel led to increased epithelium-lamina propria ratio while iron deposition was impaired. Gene expression analysis revealed elevated levels of angiogenic vascular endothelial growth factor in the clopidogrel group. Improved endothelial function was shown by immunohistochemistry (CD31, inducible nitric oxide synthase). CONCLUSIONS: Continuous administration of clopidogrel significantly improved tissue oxygenation, limited microvascular leakiness, and prevented airway ischemia. These data demonstrate that clopidogrel ameliorates microvascular injury during acute airway rejection, which is a known predisposing factor for the development of CLAD.
CRIS-Team Scopus Importer:2019-05-17

Procurement regimens to reduce ischemia reperfusion injury of vascular grafts - Abele-Ohl, S.; Heim, Christian; Eckl, Stefanie; Weyand, Michael; Stamminger, Thomas; Ensminger, S. M. (European Surgical Research, 2012)
Background: Ischemia reperfusion injury is an important nonimmunological factor contributing to the development of chronic rejection. The aim of this study was to compare different cell culture media in terms of vascular lesion formation after ischemia reperfusion injury. Methods: BALB/c aortic grafts were incubated in different cell media (endothelial cell growth, ECG, RPMI-1640 and Waymouth/Ham's F12) for various time spans (5, 6.5 and 8.5 h) at 37°C and implanted into syngeneic BALB/c recipients. On day 30 after implantation, histology, immunofluorescence and morphometric measurements were performed. Results: A total of 36 transplants were performed for this study with an overall survival rate of 72.2%. The most frequent complication was thrombosis of the aortic graft (n = 9) and there was one late death due to other courses. All the recipients with vascular grafts incubated in the ECG medium survived and showed no signs of intimal proliferation independent of the time of ischemia. Aortic grafts incubated in the RPMI medium resulted in a reduced recipient survival rate of 66.7% and grafts incubated in the Waymouth medium showed only a 50% survival by day 30. Analysis of the vascular morphology revealed moderate amounts of intimal proliferation within two aortic grafts in this group. CD31 staining revealed superior endothelial cell integrity after incubation with the ECG medium. Conclusions: Data from the current study suggest that under optimized conditions vascular grafts can be safely kept in tissue culture up to 8.5 h without significant ischemic damage. Differences in vascular integrity and animal survival depended mostly on the respective tissue culture medium used for the storage of the vessel. © 2012 S. Karger AG, Basel.
CRIS-Team Scopus Importer:2024-06-04
Keywords: Endothelial cell integrity; Ischemia reperfusion injury; Tissue culture medium; Transplant arteriosclerosis; Vascular grafts

Prolapsing Left Atrial Mass Presenting as Syncope - Pathare, Presheet; Weyand, Michael; Heim, Christian (Thoracic and Cardiovascular Surgeon Reports, 2022)
Background Myxomas are the most common primary cardiac tumor in adults and are most commonly found within the left atrium. These are usually asymptomatic, detected incidentally, or present gradually with symptoms typical of heart failure.
CRIS-Team WoS Importer:2022-07-29

Prolyl-hydroxylase inhibitor activating hypoxia-inducible transcription factors reduce levels of transplant arteriosclerosis in a murine aortic allograft model - Heim, Christian; Bernhardt, Wanja; Jalilova, Sabina; Wang, Zhendi; Motsch, Benjamin; Ramsperger-Gleixner, Martina; Burzlaff, Nicolai; Weyand, Michael; Eckardt, Kai-Uwe; Ensminger, Stephan M. (Interactive Cardiovascular and Thoracic Surgery, 2016)
The development of transplant arteriosclerosis, the hallmark feature of heart transplant rejection, is associated with a chronic immune response and also influenced by an initial injury to the graft through ischaemia and reperfusion. Hypoxia-inducible transcription factor (HIF)-1 pathway signalling has a protective effect against ischaemia-reperfusion injury and has already been demonstrated to ameliorate allograft nephropathy in previous animal studies. Therefore, the aim of this study was to investigate the effect of stabilization of hypoxia-inducible transcription factors with a prolyl-hydroxylase domain (PHD) inhibitor on transplant arteriosclerosis in an experimental aortic allograft model.MHC-class I mismatched C.B10-H2(b)/LilMcdJ donor thoracic aortas were heterotopically transplanted into the abdominal aorta of BALB/c mice. Donor animals received a single dose of the PHD inhibitor 2-(1-chloro-4-hydroxyisoquinoline-3-carboxamido) acetate (ICA) (40 mg/kg) or vehicle i.p. 4 h before transplantation. Intragraft HIF accumulation after ICA treatment was detected by immunohistochemistry before and after cold ischaemia (n = 5). Grafts were harvested 30 days after transplantation and analysed by histology (n = 7) and immunofluorescence (n = 7). In addition, intragraft mRNA expression for cytokines, adhesion molecules and growth factors was determined on Day 14 (n = 7).Donor preconditioning with ICA resulted in HIF accumulation in the aorta and induction of the HIF target genes vascular endothelial growth factor and transforming growth factor-beta. Vascular lesions were present in both experimental groups. However, there was significantly reduced intimal proliferation in preconditioned grafts when compared with vehicle controls [intimal proliferation 31.3 ± 8% (ICA) vs 55.3 ± 20% (control), P < 0.01]. In addition, experimental groups revealed a down-regulation of E-selectin (-57%) and MCP1 (-33%) expression after ICA pretreatment compared with controls, going along with decreased T-cell [1.4% CD4+ T-cell infiltration vs 8.4% (control) and 4.9% CD8+ T-cell infiltration vs 10.7% (control)], dendritic cell (0.6% dendritic cells infiltration vs 1.9% infiltration(control)] and macrophage infiltration [4.8% macrophages (ICA) vs 10.9% (control)] within vascular grafts.These data of an animal transplant model show that the pharmaceutical activation of HIF with endogenous up-regulation of protective target genes leads to adaptation of the graft to low oxygen-saturation and hereby attenuates the development of transplant arteriosclerosis and allograft injury. Pharmaceutical inhibition of PHDs appears to be a very attractive strategy for organ preservation that deserves further clinical evaluation.
EVALuna2:3838

Prospective single-centre clinical observational study on electronically monitored medication non-adherence, its psychosocial risk factors and lifestyle behaviours after heart transplantation: A study protocol - Lieb, Marietta; Weyand, Michael; Seidl, Margot; Erim, Yesim (BMJ Open, 2020)
Introduction In heart transplant recipients (HTRs), non-adherence (NA) to immunosuppressive (IS) medication and to recommended lifestyle behaviours are a common phenomenon and associated with higher risk of allograft rejection, organ loss and mortality. Risk factors for NA are highly diverse and still insufficiently researched. Precise measures of NA and an accurate understanding of its aetiology are of undisputable importance to detect patients at risk and intervene accordingly. The aim of this study is to assess the accuracy and concordance of different measures for NA as well as to determine potential risk factors. Methods and analysis This is a single-centre prospective observational trial. HTRs who are at least aged 18 are no less than 6 months post-transplant and receive tacrolimus (Prograf or Advagraf), cyclosporine (Sandimmun) or everolimus (Certican) as their prescribed IS medication are eligible for participation. We only include patients during the phase of medication implementation. At study enrolment, we assess depression, health-related quality of life, self-efficacy, social support, attachment, experiences and attitudes towards IS medication, emotional responses after transplantation, satisfaction with information about IS medication and perceptions and beliefs about medications. We further ask patients to rate their lifestyle behaviours concerning alcohol, smoking, diet, physical activity, sun protection and appointment keeping via questionnaires. Three different measurement methods for NA are applied at T0: self-reports, physician's estimates and IS trough levels. NA is monitored prospectively using an electronic multicompartment pillbox (MEMS, VAICA) over a 3-month period. Meanwhile, participants receive phone calls every second week to obtain additional self-reports, resulting in a total of seven measurement points. Ethics and dissemination The study was approved by the Clinical Ethics Committee of the University Hospital Erlangen (Friedrich-Alexander-University, Erlangen-Nürnberg). Written informed consent is attained from all participants. The results of this study will be published in peer-reviewed journals and presented at conferences. Trial registration number DRKS00020496.
CRIS-Team Scopus Importer:2020-10-23
Keywords: cardiology; statistics & research methods; transplant medicine

Quality of life in adults with congenital heart disease with and without pulmonary hypertension: a comparative study - Freiberger, Annika; Busse, Amely; Ewert, Peter; Huntgeburth, Michael; Kaemmerer, Harald; Kohls, Niko; Nagdyman, Nicole; Richter, Cristina; Roehrich, Christina; Von Scheidt, Fabian; Weyand, Michael; Freilinger, Sebastian; et al. (Cardiovascular Diagnosis and Therapy, 2022)
Background: Pulmonary vascular disease and pulmonary hypertension (PH) belong to the most relevant complications of congenital heart disease (CHD) in the long-term course. Although PH might lead to a severely impaired quality of life (QOL), there are no current studies comparing QOL in adults with CHD (ACHD) with and without PH. Therefore, this study aimed to systematically examine QOL in ACHD with and without PH in order to generate a more differentiated understanding of their overall health-status and to employ newly gained findings into general care of this particular patient population.Methods: In this comparative cross-sectional study, a representative sample of 803 adults with various forms of CHD with or without PH was analyzed. Data collection took place between September 2017 until February 2018 in a tertiary care center for ACHD. Medical data was retrieved from medical records. QOL was assessed using the EQ-5D-5L questionnaire. Descriptive methods, chi-square and t-tests were used to compare QOL of patients with and without PH.Results: Of 803 patients, 752 patients had no PH [93.6%; 47.3% female; mean age: 34.9 +/- 11.83 (range, 18-86) years], 51 were identified with manifest PH [6.4%; 55.8% female; mean age: 41.9 +/- 12.17 (range, 21-69) years]. PH patients showed significantly worse overall QOL [mean no PH: 86.78 +/- 13.30 (8.2-100) vs. mean PH: 81.79 +/- 12.77 (43.6-100); 95% confidence interval (CI): 1.43 to 9.46; P=0.013], worse crosswalk index [mean no PH: 93.29 +/- 12.86 (-11, 100) vs. mean PH: 89.73 +/- 11.77 (47-100); 95% CI: 0.08 to 7.56; P=0.043], and worse VAS [mean no PH: 80.12 +/- 16.50 (15-100) vs. mean PH: 72.56 +/- 16.80 (40-100); 95% CI: 3.29 to 12.17; P=0.004]. However, after adjusting for age, only the VAS stayed significant (P=0.039). The QOL within the dimensions mobility (P<0.001), self-care (P=0.002), and usual activities (P=0.007), were significantly decreased in PH patients. Overall, anxiety and depression (11.08%) as well as pain and discomfort (11.03%) were the most impaired dimensions in both patient groups.Conclusions: Since QOL is a significant predictor of outcome, PH-CHD patients need an early provision of psychosocial, health promoting support in addition to dedicated care and targeted PH treatment. It is therefore pivotal to timely identify unique psychosocial impairments in order to enhance quantity and QOL in this particularly vulnerable patient population.
CRIS-Team WoS Importer:2023-02-24

Quality of life in patients with Marfan syndrome: A cross-sectional study of 102 adult patients - Andonian, Caroline; Freilinger, Sebastian; Achenbach, Stephan; Ewert, Peter; Gundlach, Ulrike; Kaemmerer, Harald; Nagdyman, Nicole; Neidenbach, Rhoia Clara; Pieper, Lars; Schelling, Jörg; Weyand, Michael; Beckmann, Jürgen (Cardiovascular Diagnosis and Therapy, 2021)
Background: Marfan syndrome (MFS) is a genetically determined multiorgan disease that leads to severe physiological and psychological impairments in adult life. Little consensus exists regarding quality of life (QOL) in individuals with MFS. The present study sought to investigate QOL in a representative cohort of adults with MFS. Methods: Patient-reported outcome measures from a representative sample of 102 adults with MFS (39.3±13.1 years of age; 40.2% female) were retrospectively analyzed and compared with those from adults with different congenital heart defects (CHD), at the German Heart Center Munich. QOL was assessed using the updated five-level version of the EQ-5D. Results: Differences between both populations were analyzed. Subjects affected by MFS reported an overall reduced QOL. Compared to CHD patients, individuals with MFS scored significantly lower in the dimensions of pain/discomfort, anxiety/depression, mobility and usual activities (P<0.05). Conclusions: Patients with MFS are at high risk for impaired QOL, especially in mental and physical domains. Psychosocial consequences of MFS cost resources for both, patients and professionals. Current findings highlight the great importance of additional psychological support to cope with disease-related challenges. Increased attention should be directed towards enhancing their subjective wellbeing to potentially improve their QOL and long-term health outcomes.
CRIS-Team Scopus Importer:2021-05-14
Keywords: EQ-5D; Marfan syndrome (MFS); Prevention; Psychological situation; Quality of life

Rare Case Report: Left Atrial Sarcoma Obstructing the Left Ventricular Inflow - Kaemmerer, Ann-Sophie; Suleiman, Mathieu; Agaimy, Abbas; Harig, Frank; Weyand, Michael; Tandler, Rene (Journal of Clinical Medicine, 2023)
Malignant cardiac tumors of the heart are extremely rare and may present tremendous diagnostic and therapeutic challenges. These tumors are able to infiltrate the heart and metastasize systemically. Early detection is often elusive as the clinical presentation is highly variable, posing significant diagnostic and therapeutic difficulties. Despite a multidisciplinary approach, the prognosis for patients with malignant cardiac tumors remains guarded. Early diagnosis and a multidisciplinary approach involving cardiac surgeons, oncologists and critical care specialists are crucial in the management of this disease. Further research is needed to better understand the pathomechanisms of tumor-related complications and to develop effective treatment strategies to improve patient outcomes. The rare case of a 78-year-old woman with left atrial tumor requiring emergency surgery for acutely developing mitral valve obstruction is presented. Pathology confirmed an undifferentiated pleomorphic sarcoma. This patient tragically did not survive, highlighting the difficulties of managing such a rare and deceptive heart disease.
CRIS-Team Scopus Importer:2023-11-10
Keywords: cardiac sarcoma; cardiac surgery; left atrial tumor; malignant cardiac tumor; undifferentiated pleomorphic cardiac sarcoma

Receptor Tyrosine Kinase Inhibitor Nintedanib as Treatment Option in Bronchiolitis Obliterans after Airway Transplantation - Heim, Christian; Mauer, J.; Kuckhahn, A.; Distler, Jörg; Spriewald, B.; Ramsperger-Gleixner, Martina; Weyand, Michael; Ensminger, S. M. (JOURNAL OF HEART AND LUNG TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2019-04-04

Recovery of a dilated left ventricle after cessation of cocaine and HVAD (TM) explanation using a titanium plug - Elbayomi, Mohamed; Weyand, Michael; Seitz, Tatjana; Heim, Christian; Steger, Katrin; Tandler, Rene (Journal of Cardiac Surgery, 2022)
The ultimate goal in the treatment of end-stage heart failure is the recovery of cardiac function following mechanical assistance of the left ventricle. The HVAD (TM) pump (HeartWare Inc.) left ventricular assist device (LVAD) can be explanted without resternotomy. This article illustrates that the usage of a custom-made mechanical plug (manufactured by INNOVO Solutions GmbH), which can be inserted into the LVAD's sewing ring, is feasible. This mechanical plug explicitly designed for device explantation is a viable alternative to the current standard of care. This article adopts a less invasive technique to explant the pump. The following case illustrates this technique.
CRIS-Team WoS Importer:2022-11-25

Reduction of INCOR® driveline infection rate with silicone at the driveline exit site - Camboni, Daniele; Zerdzitzki, Matthaeus; Hirt, Stephan; Tandler, Rene; Weyand, Michael; Schmid, Christof (Interactive Cardiovascular and Thoracic Surgery, 2017)
Objectives: A silicone interface at skin level of left ventricular assist device (LVAD) may reduce the risk of driveline (DL) exit site infections when compared with other materials (e.g. velour). The purpose of this study was to evaluate the rate of DL exit site infection according to the presence of silicone or velour at the exit site with the redesigned INCOR, facilitating the positioning of silicone at the exit site. Methods: The rate of DL exit site infection and overall survival were compared between the two groups (silicone group, n = 16/velour group, n = 24) with 1-year follow-up postimplantation. Results: Risk factors for infection were more prevalent in the silicone group (obesity P = 0.33, prevalence of renal dysfunction P = 0.007, higher CRP levels P = 0.001). During the observation period, 6 patients developed a DL infection (25%) in the velour group, whereas 1 patient developed a DL infection in (6%) in the silicone group (P = 0.19). The event-per-patient year (EPPY) rates were 0.34 and 0.10 for velour group and silicone group, respectively (P = 0.30). All DL infections could be treated successfully by the antibiotic treatment, surgical debridement and ultimately high urgency heart transplantation, resulting in no direct DL infection-related mortality in this cohort. One-year survival was similar in both the groups (silicone 69 vs 75% in the velour group; P = 0.67). Conclusions: Fewer infections were observed at the exit site in case of a silicone-covered DL, without reaching statistical significance. More patients and longer observation periods are needed to demonstrate a statistical difference.
EVALuna2:102192

Reduction of obliterative bronchiolitis (OB) by prolyl-hydroxylase-inhibitors activating hypoxia-inducible transcription factors in an experimental mouse model - Heim, Christian; Motsch, Benjamin; Jalilova, Sabina; Bernhardt, Wanja M.; Ramsperger-Gleixner, Martina; Burzlaff, Nicolai; Weyand, Michael; Eckardt, Kai-Uwe; Ensminger, Stephan (Transplant Immunology, 2016)
Obliterative bronchiolitis (OB) is the major limiting factor for long-term survival after lung transplantation. As previously shown, donor treatment with a PHD-inhibitor activating hypoxia-inducible transcription factors (HIFs) prevents graft injury both in an allogenic kidney and aortic allograft transplant model. The aim of this study was to investigate the effect of HIF activation with a PHD-inhibitor on the development of OB.Fully MHC-mismatched C57BL/6 (H-2(b)) donor tracheas were orthotopically transplanted into CBA/J (H-2(k)) recipients. Donor animals received a single dose of PHD-inhibitor 2-(1-chloro-4-hydroxyisoquinoline-3-carboxamido) acetate (ICA) (40mg/kg i.p.) or vehicle control 4h before transplantation. Transplanted tracheas were harvested 14 or 30days after transplantation and were analyzed by histology, by immunofluorescence and by rtPCR for mRNA expression.Donor pre-conditioning with ICA resulted in HIF accumulation and induction of HIF target genes: HO-1, VEGF, MIF, TGF?, and EpoR, which persisted during different times of ischemia. Grafts of vehicle treated controls showed substantially more luminal obliteration on postoperative day 30 in contrast to groups pre-treated with ICA [luminal obliteration 29.2±5% (ICA) vs. 36.7±8% (control), p<0.01]. We found significantly lower expression of TNF?, PDGFß, MCP-1, E-selectin, and ICAM-1 14days after ICA premedication. In addition ICA pre-treated groups revealed decreased T-cell and macrophage infiltration in tracheal grafts on days 30 after transplantation (p<0.05).Pre-treatment with ICA effectively reduced obliterative bronchiolitis. Our data suggest that activation of hypoxia-inducible transcription factors (HIFs) and thereby adaptation to low oxygen prevents the development of OB and allograft injury. Pharmaceutical inhibition of PHDs appears to be an attractive strategy for organ preservation that deserves further clinical evaluation.
EVALuna2:3922

Repeated CXCR4 Blockade by Plerixafor Attenuates Transplant Vasculopathy in Murine Aortic Allografts - Theil, Frank; Kuckhahn, Annika; Hörning, André; Völkl, Simon; Knab, Katharina; Fritz, Niklas; Gräbner, Cindy; Ramsperger-Gleixner, Martina; Weyand, Michael; Heim, Christian (Journal of Immunology, 2024)
Plerixafor, a hematopoietic stem cell mobilization agent, increases the peripheral blood content of effector and regulatory T cells and may have beneficial effects on cardiac allograft vasculopathy. The aim of the current study was to evaluate its effects in a murine aortic allograft model using different application procedures. Allogeneic donor aorta grafts (n 5 8/group) from C57BL/6 mice(H2b) were abdominally transplanted into CBA mice (H2k). Plerixafor application was performed either continuously for 14 d using abdominally implanted osmotic pumps (1 mg/kg/d) or i.p. with a single dose (1 and 5 mg/kg) on day 0 or pulsed injections of 1 mg/kg on days 0, 7, 14, and 21. Cell distribution was monitored by FACS. Aortic grafts were evaluated for neointima development by Elastica-van-Gieson on day 30. Immunofluorescence and intragraft gene expression analysis were performed. On day 14, significantly fewer hematopoietic stem cells were found in the bone marrow of all plerixafor-treated mice. In the pulsed application group, significantly more hematopoietic stem cells were found in the peripheral blood on day 14 (0.045 ± 0.002%; p < 0.01 [pulsed]; versus 0.0068 ± 0.002% [control]) and also more regulatory T cells. PCR revealed lower inflammatory cytokines. The luminal occlusion was significantly reduced in the pulsed treated group (33.65 ± 8.84 versus 53.13 ± 12.41) going along with decreased neointimal CD4+ T cell and plasmacytoid dendritic cell infiltration, as well as less smooth muscle cell proliferation. The application of plerixafor attenuates chronic rejection in aortic allografts via immunomodulatory effects. Injection of repeated low-dose plerixafor is the most effective application form in the aortic transplant model.
CRIS-Team Scopus Importer:2024-11-22

Results from a multicentre evaluation of plug use for left ventricular assist device explantation - Potapov, Evgenij V.; Politis, Nikolaos; Karck, Matthias; Weyand, Michael; Tandler, René; Walther, Thomas; Emrich, Fabian; Reichenspurrner, Hermann; Bernhardt, Alexander; Barten, Markus J.; Svenarud, Peter; Gummert, Jan; et al. (Interactive Cardiovascular and Thoracic Surgery, 2022)
OBJECTIVES: Myocardial recovery allows for left ventricular assist device (LVAD) explantations after long-term support. Several surgical approaches, including interventional decommissioning, off-pump explantation using a custom-made plug and complete LVAD removal through redo sternotomy, have been described. We present the results from an evaluation of the long-term follow-up of patients who received a titanium sintered plug after LVAD explantation. METHODS: We performed a retrospective, European, multicentre analysis of patients who received a titanium sintered plug to seal the apical fixation ring after LVAD explantation. Data were collected from a questionnaire that included demographics, procedural details and follow-up information. RESULTS: Out of 54 contacted centres in 12 countries (n = 179 patients), a total of 68 patients were successfully included in the study. The median follow-up was 34 months (interquartile range: 17-58.5 months); 57 (84%) patients had >1-year follow-up. At the time of the last follow-up, 55 (81%) patients were alive, with a Kaplan-Meier 1-year survival of 90.1% (95% confidence interval: 84.0-98.1%) and a 5-year survival of 80.0% (95% confidence interval: 68.4-92.9%). One patient (1.5%) developed a plug infection originating from an infected part of the incorporated driveline and, after complete removal, is currently in good condition. No postoperative stroke has been reported after plug implantation. CONCLUSIONS: In this European multicentre study, the use of a custom-made titanium plug to close the apical fixation ring after LVAD explantation resulted in a low incidence of plug-related complications. With the volume of patients undergoing LVAD explantations after myocardial recovery increasing, the plug has evolved as a simple alternative to more invasive device explantation procedures or decommissioning with a high risk for infection of the remaining system or stroke.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Explantation; Left ventricular assist device; MCS; Plug; Recovery; Weaning

Results of Multicenter Evaluation of Plug Use for LVAD Explantation - Potapov, E.; Politis, N.; Rieger, S.; Karck, M.; Weyand, Michael; Walther, T.; Emrich, F.; Reichenspurrner, H.; Bernhadt, A.; Barten, M. J.; Svenarud, P.; Gummert, J.; et al. (JOURNAL OF HEART AND LUNG TRANSPLANTATION, 2021)
CRIS-Team WoS Importer:2021-04-23

Retrograde washout of prepump LVAD thrombosis in a patient on HeartWare™ support - Elbayomi, Mohamed; Weyand, Michael; Heim, Christian; Steger, Katrin; Tandler, Rene (Journal of Cardiac Surgery, 2022)
The success of the left ventricular assist device (LVAD) as a treatment for terminal left-side heart failure is still restrained by some severe complications associated with mechanical circulatory support. Pump thrombus still affects many patients. It is associated with high morbidity and mortality. The therapeutic options include augmentation of anticoagulation and antiplatelet medication, intravenous or catheter-guided thrombolysis, and pump exchange. Heart transplantation would be a desirable option in this population, but unfortunately, it is only theoretical given the increasing number of LVAD implants and decreasing number of organ donors. A retrograde washout maneuver may be a treatment option in prepump thrombosis in selected patients. Therefore, the decision should be made on an individual basis after balancing the risks and benefits of different treatment approaches. In this context, we report a case of retrograde washout of prepump thrombus in a patient who has been on HeartWare™ support for more than 3 years, with a successful bailout strategy.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Medtronic/HeartWare HVAD; peripheral thromboembolism; retrograde washout; thrombus; ventricular assist device

Role of CMV chemokine receptor M33 in airway graft rejection in a mouse transplant model - Hanka, Isabella; Stamminger, Thomas; Ramsperger-Gleixner, Martina; Kuckhahn, Annika V.; Müller, Regina; Weyand, Michael; Heim, Christian (Transplant Immunology, 2021)
Background: Cytomegalovirus (CMV) infection is a risk factor for bronchiolitis obliterans (BO), one form of chronic lung allograft dysfunction (CLAD). The viral chemokine receptor M33 is essential for successful spread of murine CMV to host salivary glands. In the present study we investigated the impact of M33 on chronic airway rejection. Methods: MHC I-mismatched tracheas of C·B10-H2b/LilMcdJ mice were transplanted into BALB/c (H2d) recipients and infected at different dates with wild type (WT) or M33-deleted (delM33) MCMV representing clinical settings of viral recipient (R)-donor (D)-serostatus: (D−/R+) or (D+/R-). Grafts were recovered for gene expression and histological / immunofluorescence analysis, respectively. Results: Evaluations showed significantly increased signs of chronic rejection in WT-infected mice compared to uninfected allografts seen in lower epithelium/lamina propria-ratio (ELR) (ELR 0.46 ± 0.07 [WT post] vs. ELR 0.66 ± 0.10 [non-inf.]; p < 0.05). The rejection in delM33-infected groups was significantly reduced vs. WT-infected groups (0.67 ± 0.04 [delM33 post]; vs. WT post p < 0.05). Furthermore, decreased rejection was observed in WT pre-infected compared to post-infected groups (0.56 ± 0.08 [WT pre]; vs. WT post p < 0.05). CD8+ T cell infiltration was significantly higher in WT-post compared to the delM33 infected or non-infected allografts. Conclusions: These data support the role of the CMV in accelerating CLAD. The deletion of chemokine receptor M33 leads to attenuated rejection.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Bronchiolitis obliterans; Chemokine receptor M33; Chronic rejection; Murine cytomegalovirus; Tracheal transplantation

Routine surveillance endomyocardial biopsy for the detection of cellular rejection beyond 2 years after cardiac transplantation - Heim, Christian; Ballazhi, Fatos; Zielezinski, Thorsten; Kondruweit, Markus; Weyand, Michael; Tandler, Rene (Journal of Cardiothoracic Surgery, 2015)
EVALuna2:16106

Single Center Experience with "Lysis First" as Treatment Strategy of Device Thrombosis in the HeartWare HVAD - Heim, Christian; Kondruweit, Markus; Weyand, Michael; Tandler, R. (2017)
EVALuna2:102191

Single-Center Retrospective Analysis of Acute Type A Aortic Dissection Outcome and Reoperation Focusing on Extended Versus Limited Initial Repair - Elbayomi, Mohamed; Weyand, Michael; Pathare, Presheet; Nooh, Ehab; Harig, Frank (Heart Surgery Forum, 2023)
Background: The optimal management strategy for acute aortic type A dissection remains controversial. Whether a limited primary (index) repair would increase the need for late aortic reintervention is still an open debate.Methods: A total of 393 consecutive adult patients with acute type A aortic dissection who underwent cardiac surgery were analyzed. Our research hypothesis was whether limited aortic index repair (i.e., isolated aorta ascending replace-ment without an open distal anastomosis with and without a concomitant aortic valve replacement, including hemiarch replacement procedure) is associated with a higher incidence of late aortic reoperation compared with extended repair (i.e., any other surgical procedure that goes beyond that limited approach).Results: Type of the initial repair had no statically sig-nificant relationship with in-hospital mortality with a P-value of 0.12, however in multivariable analysis, cross-clamp time had a statistically significant relation with mortality (P = 0.4). From the patients who survived until discharge (N = 311), 40 patients needed a reoperation on the aorta; the mean interval until reoperation was 4.5 years. The relationship between the type of the initial repair and the need for reoperation didn't reach a statically significant value (P = 0.9). In-hospitable mortality after the second operation was 10% (N = 4).Conclusion: We reached two conclusions. 1) An extended prophylactic repair in the initial operation of an acute type A aortic dissection might not lead to a lower incidence of reoperations on the aorta and could increase in-hospital mor-tality by increasing cross-clamp time, and 2) Reoperation on the aorta could be done safely with acceptable mortality outcomes.
CRIS-Team WoS Importer:2023-03-31

Single Centre Experience with Prolonged Waiting Time on Transplant List with "High-Urgency" Status - Heim, Christian; Nooh, Ehab; Kondruweit, Markus; Weyand, Michael; Tandler, Rene (Thoracic and Cardiovascular Surgeon, 2013)

Small Molecule Tyrosine Kinase Inhibitor Nintedanib Reduces Development of Cardiac Allograft Vasculopathy in Murine Aortic Allografts - Gocht, Annika; Spriewald, Bernd; Distler, Jörg; Ramsperger-Gleixner, Martina; Ensminger, Stephan M.; Weyand, Michael; Heim, Christian (Transplantation Direct, 2018)
Background: Nintedanib is a small molecule tyrosine kinase inhibitor that blocks the action of the platelet-derived growth factor receptor (PDGFR), the vascular endothelial growth factor receptor (VEGFR) and the fibroblast growth factor receptor. All of these receptors have been shown to be involved in the development of cardiac allograft vasculopathy (CAV) after heart transplantation. We therefore hypothesized that blocking these tyrosine kinase receptors with nintedanib could prevent CAV. Methods: CBA/JRj (H2k) mice underwent an abdominal aortic transplantation with a graft derived from fully allogeneic C57BL/6JRj (H2b) mice. Nintedanib was given daily from the first day after transplantation until harvest on day 14 for polymerase chain reaction analysis of intragraft cytokine expression or harvest on day 30 for histological analysis of the graft. Results: Nintedanib treatment resulted in significantly reduced neointima formation in the aortic graft compared with untreated control allografts. Interestingly, the immigration of smooth muscle cells into the neointima was markedly reduced while graft infiltrating macrophages and T cells were not altered in nintedanib-treated animals. The expression of the growth factor PDGF was significantly reduced in the nintedanib group going along with a distinctly reduced expression of the corresponding receptors PDGFR α and -β. Conclusions: Treatment with nintedanib caused a significant reduction of CAV development after aortic transplantation in mice. We hypothesize the attenuated neointima formation in nintedanib-treated animals to be mediated by a direct inhibition of intimal smooth muscle cell proliferation via reduced expression of PDGF and the appropriate receptors PDGFR α + β.
EVALuna2:34648

Stem Cell Mobilization by Plerixafor Has an Affirmatory Effect on the Development of Transplant Vasculopathy in a Murine Aortic Allograft Model - Theil, F.; Kuckhahn, A.; Hörning, André; Ramsperger-Gleixner, Martina; Weyand, Michael; Heim, Christian (JOURNAL OF HEART AND LUNG TRANSPLANTATION, 2022)
CRIS-Team WoS Importer:2022-05-20

Sternal osteomyelitis - Surgical treatment concepts - Beier, Justus; Arkudas, Andreas; Lang, Werner; Weyand, Michael; Horch, Raymund E. (Chirurg, 2016)
Sternal osteomyelitis is a potentially fatal condition following cardiac surgery. Sternal osteomyelitis should be diagnosed as early as possible followed by an interdisciplinary radical debridement. Subsequently plastic reconstructive surgery is necessary for defect reconstruction. This can be achieved by a number of established pedicled and free flap plastic surgery procedures. The choice of flap procedures is based on defect geometry and the individual patient situation, including potential flap donor sites. Smaller defects can generally be reconstructed by pedicled flap transfer. For extensive sternal defects, free flap transplantation is now a well-established therapeutic option. In some patients lacking sufficient recipient vessels, the creation of an arteriovenous (AV) loop as recipient vessel is necessary. In summary, successful therapy of sternal osteomyelitis is based on early interdisciplinary treatment by the various surgical subspecialties.
EVALuna2:15235

Successive surgical repair of a progressive aortic dissection in a case of Loeys–Dietz Syndrome - Pathare, Presheet; Elbayomi, Mohamed; Tandler, Rene; Weyand, Michael; Harig, Frank (Journal of Cardiac Surgery, 2022)
Introduction: The Frozen Elephant Trunk technique is a well-established treatment for aortic dissections (Stanford Type A) involving the aortic arch and descending aorta. The Thoraflex™ Hybrid prosthesis (Vascutek Ltd.), consisting of a proximal flexible conduit and a distal self-expanding covered stent, has consistently shown positive results in the treatment of this condition. Case Description: The following is a description of such a staged reconstruction using the Thoraflex™ Hybrid Ante-Flo™ device, performed in a patient previously diagnosed with Loeys–Dietz Syndrome. After clamping the aorta proximally, an incision was taken at the distal end of the stent. Here, the distal end of the new prosthesis was inserted into the true lumen of the descending aorta and the stent was deployed. Following this, a bypass was established via the left atrium, and blood was returned to the lower body using the perfusion arm of the prosthesis with the proximal part of the descending aorta clamped. The collar of the prosthesis was sutured proximally to the aorta near the inlying previous stent. Air was removed via the perfusion arm of the prosthesis, which was then oversewn. Discussion: To date, hybrid prostheses have only been used on the proximal aorta in patients with aortic aneurysms and aortic dissections (Stanford Type A). Conclusion: Using the described technique, it is possible to reconstruct the aortic anatomy using the available prostheses with accuracy and minimal complications.
CRIS-Team Scopus Importer:2022-12-02
Keywords: aorta and great vessels; perfusion

Support Pressure Acting on the Epicardial Surface of a Rat Left Ventricle — A Computational Study - Martonová, Denisa; Holz, David; Brackenhammer, Dorothea; Weyand, Michael; Leyendecker, Sigrid; Alkassar, Muhannad (Frontiers in Cardiovascular Medicine, 2022)
The present computational study investigates the effects of an epicardial support pressure mimicking a heart support system without direct blood contact. We chose restrictive cardiomyopathy as a model for a diseased heart. By changing one parameter representing the amount of fibrosis, this model allows us to investigate the impairment in a diseased left ventricle, both during diastole and systole. The aim of the study is to determine the temporal course and value of the support pressure that leads to a normalization of the cardiac parameters in diseased hearts. These are quantified via the end-diastolic pressure, end-diastolic volume, end-systolic volume, and ejection fraction. First, the amount of fibrosis is increased to model diseased hearts at different stages. Second, we determine the difference in the left ventricular pressure between a healthy and diseased heart during a cardiac cycle and apply for the epicardial support as the respective pressure difference. Third, an epicardial support pressure is applied in form of a piecewise constant step function. The support is provided only during diastole, only during systole, or during both phases. Finally, the support pressure is adjusted to reach the corresponding parameters in a healthy rat. Parameter normalization is not possible to achieve with solely diastolic or solely systolic support; for the modeled case with 50% fibrosis, the ejection fraction can be increased by 5% with purely diastolic support and 14% with purely systolic support. However, the ejection fraction reaches the value of the modeled healthy left ventricle (65.6%) using a combination of diastolic and systolic support. The end-diastolic pressure of 13.5 mmHg cannot be decreased with purely systolic support. However, the end-diastolic pressure reaches the value of the modeled healthy left ventricle (7.5 mmHg) with diastolic support as well as with the combination of the diastolic and systolic support. The resulting negative diastolic support pressure is −4.5 mmHg, and the positive systolic support pressure is 90 mmHg. We, thereby, conclude that ventricular support during both diastole and systole is beneficial for normalizing the left ventricular ejection fraction and the end-diastolic pressure, and thus it is a potentially interesting therapy for cardiac insufficiency.

Systematic assessment of health care perception in adults with congenital heart disease in Germany - Neidenbach, Rhoia; Achenbach, Stephan; Andonian, Caroline; Bauer, Ulrike M.M.; Ewert, Peter; Freilinger, Sebastian; Gundlach, Ulrike; Kaemmerer, Ann Sophie; Nagdyman, Nicole; Nebel, Kathrin; Oberhoffer, Renate; Pieper, Lars; et al. (Cardiovascular Diagnosis and Therapy, 2021)
Background: The number of adults with congenital heart disease (ACHD) is steadily rising due to increased survival rate and improved medical resources. Accordingly, more than 330,000 ACHD are currently living in Germany. Almost all of them require lifelong specialized medical follow-up for their chronic heart disease, often accompanied by residua, sequelae, or comorbidities. Primary care physicians (PCPs) are a crucial factor in directing patients to ACHD specialists or specialized institutions, but despite all efforts, the number of ACHD under specialized care is low, the lost-to-follow-up rate is high, and the morbidity and mortality is substantial. The present cross-sectional study was designed to systematically characterize the health care of ACHD from a patient perspective, including (I) use of medical care by ACHD, (II) medical counselling needs, and (III) perceived satisfaction with health care. Methods: The German-wide analysis was based on a 25-item questionnaire designed to address different aspects of medical status and health issues of ACHD from their own perspective, performed between May of 2017 and July of 2020. Results: A total of 4,008 ACHD (52% female; mean age 41.9±17.2 years) completed the questionnaire. The majority of ACHD (3,524, 87.9%) reported, that they consulted their PCP for non-cardiac health problems, and 49.7% (n=1,991) consulted their PCP also for medical problems associated with the underlying CHD. Almost all ACHD reported a need for medical advice concerning exercise capacity and daily life activities, occupational skills, pregnancy, rehabilitation, genetic counselling, insurance, and retirement. A total of 1,840 (45.9%) patients were not aware of the existence of certified ACHD specialists or centers. Moreover, 2,552 (67.6%) of those surveyed were uninformed about patient organizations for ACHD. Conclusions: The present study demonstrates that ACHD are largely uninformed about the ACHD care structures available nationwide, although the patients have a great need for specialized follow-up, advice, and care.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Adults with congenital heart disease (ACHD); Congenital heart disease (CHD); General practitioners; Medical health supply; Primary care physicians (PCPs); Primary health care

The Canonical Wnt Pathway in the Pathogenesis of Cardiac Allograft Vasculopathy - Kuckhahn, A.; Ramsperger-Gleixner, Martina; Distler, Jörg; Spriewald, B.; Ensminger, S.; Weyand, Michael; Heim, Christian (JOURNAL OF HEART AND LUNG TRANSPLANTATION, 2020)
CRIS-Team WoS Importer:2020-04-24

The Canonical Wnt Pathway in the Pathogenesis of Cardiac Allograft Vasculopathy - Kuckhahn, A.; Ramsperger-Gleixner, Martina; Distler, Jörg; Spriewald, B.; Ensminger, S.; Weyand, Michael; Heim, Christian (Journal of Heart and Lung Transplantation, 2020)
PURPOSE: The canonical wnt pathway with its central signaling molecule β-catenin is important for tissue development and homeostasis and its dysregulation leads to many diseases including pathologies of the cardiovascular system. Inhibition of the wnt pathway has the potential to protect against cardiac allograft vasculopathy (CAV), because it reduces the proliferation of smooth muscle cells (SMCs), which is a main pathomechanism of CAV and causes neointima formation and vessel occlusion. METHODS: For in vitro experiments human (hu) and murine (mu) aortic SMCs were grown in the presence of increasing concentrations of wnt inhibitors, such as XAV-939, ICG-001 or PKF118-310. Cell proliferation was measured as the extent of PrestoBlue Cell Viability Reagent metabolism and expression of representative wnt target genes was assessed by Taqman PCR. Additionally, the wnt inhibitors were used in the mouse model of aortic transplantation (n=8 mice/group) and the extent of neointima formation as an indicator for CAV was analyzed. We also measured the expression of β-catenin (immunofluorescence staining), wnt target genes (Taqman PCR) and several inflammatory cytokines (Taqman PCR) in the transplant. RESULTS: In vitro experiments revealed dose-dependent proliferation inhibition in huSMCs and muSMCs after treatment with each wnt inhibitor. PKF118-310 induced cell death in the highest concentrations tested. While XAV-939 had only minor influence on the expression of the wnt target genes cyclin D1, axin2 and p21, ICG-001 and PKF118-310 induced the expression of p21 and cyclin D1 and reduced the expression of axin2. Interestingly, in vivo experiments showed no effect of XAV-939 and ICG-001 on neointima formation, whereas neointimal amounts of β-catenin were significantly reduced. ICG-001 also reduced the expression of inflammatory cytokines (INFγ, TNFα and IL-6) and of p21, but did not influence cyclin D1 expression. XAV-939 had no relevant influence on cytokine expression. Results for PKF118-310 and wnt target gene expression in transplants after XAV-939 treatment are currently assessed. CONCLUSION: Strong anti-proliferative effects were found in vitro for all three wnt inhibitors, but this did not lead to reduced CAV development in a mouse model of vessel transplantation. Effects on SMCs themselves after ICG-001 and PKF118-310 seem indeed mediated via regulation of wnt target genes.
CRIS-Team Scopus Importer:2020-06-09

The Degree of t-System Remodeling Predicts Negative Force-Frequency Relationship and Prolonged Relaxation Time in Failing Human Myocardium - Abu-Khousa, Maha; Fiegle, Dominik; Sommer, Sophie T.; Minabari, Ghazali; Milting, Hendrik; Heim, Christian; Weyand, Michael; Tomasi, Roland; Dendorfer, Andreas; Volk, Tilmann; Seidel, Thomas (Frontiers in Physiology, 2020)
The normally positive cardiac force-frequency relationship (FFR) becomes flat or negative in chronic heart failure (HF). Here we explored if remodeling of the cardiomyocyte transverse tubular system (t-system) is associated with alterations in FFR and contractile kinetics in failing human myocardium. Left-ventricular myocardial slices from 13 failing human hearts were mounted into a biomimetic culture setup. Maximum twitch force (F), 90% contraction duration (CD90), time to peak force (TTP) and time to relaxation (TTR) were determined at 37°C and 0.2–2 Hz pacing frequency. F1Hz/F0.5Hz and F2Hz/F0.5Hz served as measures of FFR, intracellular cardiomyocyte t-tubule distance (ΔTT) as measure of t-system remodeling. Protein levels of SERCA2, NCX1, and PLB were quantified by immunoblotting. F1Hz/F0.5Hz (R2 = 0.82) and F2Hz/F0.5Hz (R2 = 0.5) correlated negatively with ΔTT, i.e., samples with severe t-system loss exhibited a negative FFR and reduced myocardial wall tension at high pacing rates. PLB levels also predicted F1Hz/F0.5Hz, but to a lesser degree (R2 = 0.49), whereas NCX1 was not correlated (R2 = 0.02). CD90 correlated positively with ΔTT (R2 = 0.39) and negatively with SERCA2/PLB (R2 = 0.42), indicating that both the t-system and SERCA activity are important for contraction kinetics. Surprisingly, ΔTT was not associated with TTP (R2 = 0) but rather with TTR (R2 = 0.5). This became even more pronounced when interaction with NCX1 expression was added to the model (R2 = 0.79), suggesting that t-system loss impairs myocardial relaxation especially when NCX1 expression is low. The degree of t-system remodeling predicts FFR inversion and contraction slowing in failing human myocardium. Moreover, together with NCX, the t-system may be important for myocardial relaxation.
CRIS-Team Scopus Importer:2020-04-14
Keywords: cardiac excitation-contraction coupling; cardiac remodeling; force frequency relationship; heart failure; human heart; transverse tubular system

The lost balloon at midnight: a case report reveals the inevitability of heart team existence - Elbayomi, Mohamed; Weyand, Michael; Nooh, Ehab; Harig, Frank (Journal of Cardiothoracic Surgery, 2023)
BACKGROUND: Dislodgement of a coronary stent-balloon catheter during percutaneous coronary intervention (PCI) is rare but is a life-threatening complication. A 57- year-old male presented with a non-ST elevation myocardial infarction (NSTEMI). Coronary angiography revealed total thrombotic occlusion of the Right coronary artery (RCA). Following the balloon dilatation of the RCA and while trying to retrieve the balloon catheter, the balloon was dislodged from the catheter shaft and entrapped in the coronary vessel. Under cardiopulmonary bypass, with antegrade cardioplegic arrest, the balloon was extracted through a coronary arteriotomy. Right coronary revascularization was done with reversed saphenous vein graft (SVG). DISCUSSION: Given the variety of equipment that can be retained in the coronary artery and the multitude of mechanisms by which it may be entrapped, there are no straightforward techniques applicable to all situations. Specific guidelines or recommendations on properly managing these potentially life-threatening complications do not exist. However, the most crucial issue in the management of these cases is the hemodynamic status of the patient as well as the coronary flow in the vessel with entrapped device or stent. In our case, the RCA was retrogradely perfused from the left coronary artery, which provided time to transfer the patient to cardiovascular surgical backup.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Cardiopulmonary bypass; Case report; Coronary artery bypass surgery; Heart team; Percutaneous coronary intervention; Unstable angina pectoris

The mystery of methylene blue and its role in managing post-cardiac surgery vasoplegic shock - Elbayomi, Mohamed; Dewald, Oliver; Pathare, Presheet; Kondruweit, Markus; Tandler, Rene; Weyand, Michael; Heim, Christian (Annals of Medicine, 2025)
Background: Vasoplegic syndrome is associated with high mortality. Methylene blue (MB) is a guanylate cyclase inhibitor that ameliorates this re-distributive type of shock. This study aims to investigate the outcome in patients who received MB early postoperatively. Methods: 2753 patients who underwent cardiac surgery utilizing cardiopulmonary bypass at our institution in a time interval of two years were identified. The incidence of vasoplegic syndrome was 7.2% (n = 200). Pharmacy records identified 84 patients (group 1, MB group) who received methylene blue and 116 patients (group 2, Control group) who didn’t receive the drug. This single-center retrospective cohort study’s primary outcome was in-hospital mortality. Secondary outcomes were postoperative hemodialysis, serum lactate levels at 24 h postoperatively, and intensive care unit stay length in days. Results: MB patients have a shorter ICU stay as compared to the control group (9 ± 8 days vs. 16 ± 6.9; p-value <.001). In the control group, postoperative hemodialysis was higher (20% in the MB group and 40% in the control group; p-value <.05). At 24 h post-op, the methylene blue group had reduced serum lactate levels (1.8 ± 1.2 vs. 4 ± 1.8 in the control group; p-value <.001). The methylene blue group had a decreased 24-hour norepinephrine dose (1.5 ± 1.2 vs. 2.8 ± 2 in the control group; p-value <.05). In-hospital mortality was not significantly different between the two groups (38% in the MB group vs. 43% in the control group). Conclusion: Early postoperative administration of methylene blue in patients with vasoplegic syndrome shortens intensive care unit stay and contributes to less end-organ damage.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Cardiopulmonary bypass; methylene blue; vasoplegic syndrome

The relation of aortic dimensions and obesity in adults with Marfan or Loeys-Dietz syndrome - Suleiman, Mathieu; Freilinger, Sebastian; Meierhofer, Christian; May, Matthias; Bischoff, Gert; Ewert, Peter; Freiberger, Annika; Huntgeburth, Michael; Kaemmerer, Ann-Sophie; Marwan, Mohamed; Nagdyman, Nicole; Roth, Jan-Peter; et al. (Cardiovascular Diagnosis and Therapy, 2022)
Background: Aortic aneurysm and aortic dissection can have a major impact on the life expectancy of Marfan syndrome (MFS) or Loeys-Dietz syndrome (LDS) patients. Although obesity can influence the development of aortic complications, evidence on whether obesity influences the development of aortic aneurysm or dissection in MFS and LDS is limited. The aim of the present study was to elucidate the relationship between aortic size and body composition, assessed by modern bioelectrical impedance analysis (BIA) in MFS/LDS-patients.Methods: In this exploratory cross-sectional study in MFS or LDS patients, enrolled between June 2020 and May 2022, 34 patients received modern BIA and magnetic resonance imaging (MRI) (n=32) or computed tomography (CT) imaging (n=2) of the entire aorta. A P value of <0.05 was considered significant.Results: Fifty-one patients (66% female; mean age: 37.7 +/- 11.7; range, 17-68 years) with MFS or LDS were enrolled; 34 patients, 27 with MFS and 7 with LDS, underwent aortic MRI or CT scanning. The mean aortic length was 503.7 +/- 58.7 mm, and the mean thoracic aortic length and abdominal aortic length were 351.5 +/- 52.4 and 152.2 +/- 27.4 mm, respectively. The aortic bulb and the ascending aorta were measured only in the non-surgically repaired patients. Fifteen MFS (88.2%) and two LDS (40.0%) patients had an aortic aneurysm. In these, the aortic bulb tended to be larger in MFS than in LDS patients [42.6x41.9x41.2 vs. 37.8x37.4x36.8 mm; P=0.07 (-1.1; 9.1); P=0.07 (-1.2; 8.4); P=0.07 (-1.5; 7.9)]. BIA revealed mean body fat levels of 31.6%+/- 8.7% (range, 9.5-53.5%), indicating that 18 patients (52.9%) were obese. There was a significant correlation between body fat content and thoracic aortic length (R=-0.377; P=0.02), muscle mass and total aortic length (R=0.359; P=0.03), thoracic aortic length (R=0.399; P=0.02), extracellular mass (ECM), and total aortic length (R=0.354; P=0.04) , connective tissue and aortic diameters at the aortic arch (R=0.511; P=0.002), aortic isthmus (R=0.565; P<0.001), and abdominal aorta (R=0.486; P=0.004). Older age was correlated with wider aortic arch, isthmus, and abdominal aorta. Male patients had a longer aorta.Conclusions: While a slender habitus is commonly known for MFS and LDS patients, our data show that many MFS and LDS patients (especially female) do not fit this phenotypic characteristic and are obese, which is associated with a more severe aortic phenotype. This topic should be included in the clinical assessment of affected MFS and LDS patients, in addition to measurement of the aortic diameters. Physicians should systematically screen MFS and LDS patients for obesity, educate them about the potential risk of resulting aortic complications, and encourage them to adopt a healthy lifestyle, that includes (mild) exercise and a balanced diet.
CRIS-Team WoS Importer:2023-02-03
Keywords: Adults with connective tissue disease; Marfan syndrome (MFS); Loeys-Dietz syndrome (LDS); body composition; obesity

Transcutaneous Energy Transfer System for Cardiac-Assist Devices by Use of Inhomogeneous Biocompatible Core Material - Fazeli Khalili, Hossein; Kirchner, Jens; Bartunik, Max; Werner, Siegfried; Ebel, Nina; Schubert, Dirk W.; Weyand, Michael; Fischer, Georg (IEEE Transactions on Magnetics, 2021)
A novel magnetic liquid silicone rubber composite core design applicable to wireless power transfer (WPT) for medical applications is presented. As a case study, the integration of WPT, including the proposed cores for the coils, with ventricular assist devices (VADs) was investigated. This facilitates transferring 4.6 W of power wirelessly through the skin-layer, which thus allows to disposal of the transcutaneous cable that connects the extracorporal batteries to the implanted blood pump. To enhance the coupling coefficient and consequently increase the WPT efficiency, the geometry of the cores was optimized. This reduces the temperature increase in the implant area. The field and thermal simulations were carried out with CST software. The electrical properties of the proposed design as obtained by simulation were validated by measurements. The simulation results perfectly coincide with the measured results. Finally, a new optimized design with additional high permeability core inserts is introduced to further increase the coupling coefficient. The results indicate that the coupling coefficient is increased from 0.31 to 0.52 with the optimized design compared to the case without cores. Moreover, by fixing the initial temperature as 37 °C, the maximum temperature is decreased from 38.19 °C to 37.27 °C, while keeping the transferred power fixed. Its high magnetic conductivity, biocompatibility, low-loss property, flexibility and Qi-standard compatibility make the proposed WPT design an excellent candidate for the wireless-powering of heart assist devices such as VAD

Transmural fibre orientations based on Laplace-Dirichlet-Rule-Based-Methods and their influence on human heart simulations - Holz, David; Martonová, Denisa; Schaller, Emely; Duong, Minh Tuan; Alkassar, Muhannad; Weyand, Michael; Leyendecker, Sigrid (Journal of Biomechanics, 2023)

Treatment of advanced heart failure in adults with congenital heart disease: a narrative review and clinical cases - Sinning, Christoph; Huntgeburth, Michael; Fukushima, Norihide; Tompkins, Rose; Huh, June; Tataneo, Shigeru; Diller, Gerhard-Paul; Chen, Yih-Sharng; Zengin, Elvin; Magnussen, Christina; Kaemmerer, Ann-Sophie; Cho, Yang Hyun; et al. (Cardiovascular Diagnosis and Therapy, 2022)
Background and Objective: The number of adults with congenital heart disease (ACHD) is increasing worldwide. Almost all congenital cardiac lesions can be successfully treated due to the progress in neonatal surgery and pediatric cardiology with a high likelihood of surviving until adulthood. However, ACHD frequently develop sequelae related to the initial cardiac anomaly. Heart failure (HF) is one of the most common complications associated with a high morbidity and mortality.Methods: The authors did search the PubMed database regarding relevant content covering publications up to March 2022. Relevant manuscripts were classified according to the impact factor of the journal, being a guideline manuscript, a position paper by a society or a comprehensive review of the current literature. Key content and findings: Optimal HF treatment remains an unmet need in ACHD. In particular, advanced HF therapy with cardiac resynchronization therapy, ventricular assist devices or organ transplantation is still very different and more specific in ACHD compared to non-ACHD. This review aims to compile international views and evidence from the literatures on the treatment of advanced HF in ACHD. Current challenges, but also the success of different treatment strategies in ACHD are illustrated by clinical cases.Conclusions: The main finding of the review is that data is still scarce regarding ACHD with advanced HF and international efforts to collect data regarding these patients needed to improve the current standard of care.
CRIS-Team WoS Importer:2022-10-21

Tyrosine Kinase Inhibitor Nintedanib Reduces Development of Transplant Vasculopathy in a Murine Aortic Transplantation Model - Gocht, A.; Ensminger, S. M.; Distler, Jörg; Spriewald, B.; Ramsperger-Gleixner, Martina; Weyand, Michael; Heim, Christian (2017)
EVALuna2:35050

Variable effects of different serotonin receptor subtype antagonists on the development of transplant vasculopathy in murine aortic allografts - Heim, Christian; Gocht, Annika; Distler, Jörg; Spriewald, Bernd; Ramsperger-Gleixner, Martina; Weyand, Michael; Ensminger, Stephan M. (2016)
EVALuna2:35070

Vascular inflammation and media calcification are already present in early stages of chronic kidney disease - Benz, Kerstin; Varga, Ildiko; Neureiter, Daniel; Campean, Valentina; Daniel, Christoph; Heim, Christian; Reimann, Albrecht; Weyand, Michael; Hilgers, Karl Friedrich; Amann, Kerstin Ute (Cardiovascular Pathology, 2017)
While patients with chronic kidney disease (CKD) have a high prevalence of classical coronary risk factors, there is increasing evidence that atherosclerosis is different in renal compared to nonrenal patients. Therefore, the present study compares changes in different vessels obtained at cardiac surgery between patients with early and advanced CKD and nonrenal control patients.Fifty patients undergoing cardiac bypass surgery were divided into three groups: (i) 24 control patients with creatinine <1.3mg/dl, (ii) 14 patients with early CKD (creatinine 1.3-2.0mg/dl), and (iii) 12 patients with advanced CKD (creatinine >2.0mg/dl). Aorta, arteria mammaria interna, and vena saphena (V. saphena) were analyzed using morphometry, Kossa stain for vascular calcification, and immunohistochemistry for markers of inflammation and proosteogenic differentiation of vascular smooth muscle cells (VSMCs). Thereby, aortic wall thickness and calcification score of aortic intima and of V. saphena were significantly higher in advanced CKD patients than in nonrenal control patients, whereas significant vascular inflammation and proosteogenic dedifferentiation of VSMC and calcification of the aortic media were already present in early CKD. Interestingly, marked calcification of the V. saphena magna was seen in advanced CKD. Of note, calcium-phosphate product correlated well with markers of inflammation, but not with calcification itself.Early stages of CKD are already associated with local up-regulation of proinflammatory and proosteogenic molecules in the vascular wall and calcification of the aortic media. These findings point to the importance of local microinflammation in CKD and may shed new light on the potentially overestimated role of the calcium-phosphate product for vessel calcification.
EVALuna2:3941

Wearable cardioverter defibrillator after cardiac surgery: Analysis of real-life data from patients at transient risk of sudden cardiac death - Elbayomi, Mohamed; Weyand, Michael; Seitz, Tatjana; Harig, Frank (Annals of Noninvasive Electrocardiology, 2023)
Background: Especially in the first 3 months after cardiac surgery, patients are at transient risk of sudden cardiac death (SCD). To close the gap between hospital discharge and the final implantable cardioverter-defibrillator (ICD) decision, guidelines recommend temporarily using a wearable cardioverter-defibrillator (WCD) to protect these patients from SCD. We investigated real-life data on the safety, effectiveness, and compliance of the WCD in this population. Methods: Data for analysis were collected via the Zoll Patient Management Network (ZPM) from patients who underwent cardiac surgery and who were discharged with a WCD between 2018 and 2021 at the Cardiac Surgery Center of the University of Erlangen in Germany. Results: The majority of the 55 patients were male (90.9%) and underwent a coronary artery bypass graft (80.0%). The number of patients with left ventricular ejection fraction (LVEF) >35% increased from 9.1% at the beginning of WCD use to 58.2% at the end of WCD use. Six ventricular tachycardia (VT) episodes occurred in four patients. The WCD appropriately defibrillated two patients with VT episodes. There were no inadequate shocks and no fatalities during the observation time. WCD wearing compliance was high, with a median wear time of 23.3 h/day. Conclusion: This retrospective analysis in a single cardiac surgery center confirms prior data on the safety and effectiveness of the WCD in patients in post-surgery care in a real-life setting. The WCD successfully protected patients from SCD during life-threatening VT episodes. WCD wearing compliance was high.
CRIS-Team Scopus Importer:2023-02-17
Keywords: heart failure; sudden cardiac death; ventricular tachycardia; wearable cardioverter defibrillator

'Well-being paradox' revisited: a cross-sectional study of quality of life in over 4000 adults with congenital heart disease - Andonian, Caroline Sophie; Freilinger, Sebastian; Achenbach, Stephan; Ewert, Peter; Gundlach, Ulrike; Hoerer, Jürgen; Kaemmerer, Harald; Pieper, Lars; Weyand, Michael; Neidenbach, Rhoia Clara; Beckmann, Jürgen (BMJ Open, 2021)
Objective The present cross-sectional study investigated quality of life (QOL) in a large cohort of German adults with congenital heart disease (ACHDs) in association with patient-related and clinical variables. Design Cross-sectional survey. Participants Between 2016 and 2019, a representative sample of 4014 adults with various forms of congenital heart defect (CHD) was retrospectively analysed. Inclusion criteria were confirmed diagnosis of CHD; participant aged 18 years and older; and necessary physical, cognitive and language capabilities to complete self-report questionnaires. Primary and secondary outcome measures QOL was assessed using the 5-level EQ-5D version (EQ-5D-5L). Sociodemographic and medical information was obtained by a self-devised questionnaire. Associations of QOL with patient-reported clinical and sociodemographic variables were quantified using multiple regression analysis and multiple ordinal logit models. Results Overall, ACHDs (41.8±17.2 years, 46.5% female) reported a good QOL comparable to German population norms. The most frequently reported complaints occurred in the dimensions pain/discomfort (mean: 16.3, SD: p<0.001) and anxiety/depression (mean: 14.3, p<0.001). QOL differed significantly within ACHD subgroups, with patients affected by pretricuspid shunt lesions indicating the most significant impairments (p<0.001). Older age, female sex, medication intake and the presence of comorbidities were associated with significant reductions in QOL (p<0.001). CHD severity was positively associated with QOL within the dimensions of self-care (OR 0.148, 95% CI 0.04 to 0.58) and mobility (OR 0.384, 95% CI 0.19 to 0.76). Conclusion Current findings temper widely held assumptions among clinicians and confirm that ACHDs experience a generally good QOL. However, specific subgroups may require additional support to cope with disease-related challenges. The negative correlation of QOL with age is especially alarming as the population of ACHDs is expected to grow older in the future. Trial registration number DRKS00017699; Results.
CRIS-Team Scopus Importer:2021-07-16
Keywords: adult cardiology; cardiac epidemiology; congenital heart disease; epidemiology; mental health; preventive medicine